Implications of Cryogenian magmatism in the light of evolutionary history of the Southern Granulite Terrane, Indian shield: a case study from Sholayar Syenite Pluton - Moumita Chowdhury; Jyotisankar Ray; Debaleena Sarkar; Suresh C. Patel; J. Amal Dev; Christian Koeberl; Anindita Dey; Desikan Ramakrishnan; Rohit Pandey; Pratik Mukherjee (Lithos, 2026)

A national health impact assessment of achieving tree canopy goals in US urban areas - Michelle C. Kondo; Tamara Iungman; Evelise Pereira Barboza; Dexter H. Locke; Ray Yeager; Dustin Fry; Ava-Clare Steed; Marcia Pescador Jiménez; David Rojas-Rueda; Mark Nieuwenhuijsen (Environmental Research, 2026)

Geometric morphometrics enables accurate predictions of palaeoecology and reveals unique adaptations to an expanded niche space in extinct waterfowl - Ray Mariano Chatterji; Shante Williams; Janet C. Buckner (Evolutionary Ecology, 2026)

Ranking primary food allergens by specific IgE-binding and clinical relevance in Dutch adults to identify reference protein sets for allergenicity assessment - Sim Ray Yue; Michelle C.L. Chou; Emily J.J. Kallen; André C. Knulst; Geert F. Houben; Katrine Lindholm Bøgh; Thuy-My Le; Kitty C.M. Verhoeckx (Food and Chemical Toxicology, 2026)

Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

Genome‐wide associations of leaf spectral variation in MAGIC lines of Nicotiana attenuata - Cheng Li; Ewa A. Czyż; Bernhard Schmid; Rishav Ray; Rayko Halitschke; Ian T. Baldwin; Michael E. Schaepman; Meredith C. Schuman (Ecology, 2026)
The application of in‐field and aerial spectroscopy to assess functional and phylogenetic variation in plants has led to novel ecological insights and supports global assessments of plant biodiversity. Understanding how plant genetic variation influences reflectance spectra will help harness this potential for biodiversity monitoring and improve understanding of why plants differ in functional responses to environmental change. Here, we use a well‐resolved genetic mapping population derived from Multiparent Advanced Generation Inter‐cross (MAGIC) lines of Nicotiana attenuata to associate genetic differences with differences in leaf spectra between plants in a field experiment in their natural environment. We analyzed the leaf reflectance spectra using a hand‐held spectroradiometer (350–2500 nm) on 616 fully genotyped plants of N. attenuata grown in a randomized block design. We tested three approaches to conducting genome‐wide association studies on spectral variants. We introduce a new hierarchical spectral clustering with parallel analysis (HSC‐PA) method. This method efficiently captured the variation in our high‐dimensional dataset and allowed us to discover a novel association, between a locus on chromosome 1 and the 734–1143 nm spectral range, spanning the red‐edge and near‐infrared regions that are sensitive to leaf structure and photosynthetic activity. This locus contains a candidate gene annotated as carbonic anhydrase, an enzyme involved in CO₂ hydration and regulation of photosynthetic efficiency, suggesting a physiological link between variation in leaf optical properties and carbon assimilation. In contrast, an approach treating single wavelengths as phenotypes identified genetic signals highly consistent with HSC‐PA, but suffered from massive statistical redundancy without pinpointing significant, interpretable features. An index‐based approach, which reduces complex spectra to a few dimensionless variables, detected two significant associations for (a water‐content‐related index) with loci on chromosome 1 near genes annotated as a Zeta toxin domain‐containing protein, and an Exocyst subunit Exo70 family protein. While these findings are biologically plausible, they represent a very narrow subset of the spectral variation captured by HSC‐PA. The HSC‐PA approach supports a comprehensive understanding of the genetic determinants of leaf spectral variation that is data‐driven but human‐interpretable and is thus a tool to discover genetic differences underlying intraspecific variation, a foundation of biodiversity.

Comparing Effectiveness of Experimental and Implemented Bycatch Reduction Measures: the Ideal and the Real - Ray Hilborn; Eric Gilman; Martin Hall; C. Tara Marshall; Edward Melvin; Maite Pons (Reviews in Fisheries Science & Aquaculture, 2026)

Decarbonizing Fisheries Through Ensuring Healthy Stock Status - Ray Hilborn; Katja Enberg; Sara Hornborg; Katherine McElroy; Michael C. Melnychuk; Robert Parker; Kim Scherrer; Peter Tyedmers; Friederike Ziegler (Fish and Fisheries, 2026)
Industrial capture fisheries depend on fossil fuels, which tend to dominate both greenhouse gas emissions and operational costs of this form of seafood production. Improving energy efficiency is, in addition to shifting to alternative fuels, a crucial path towards decarbonizing fisheries. Theory suggests that healthy stocks, i.e., with higher density, should require less fuel to harvest when fishing effort and catches are correlated. This is a situation generally observed in bottom trawl fisheries. Rebuilding stocks could thus represent an important pathway for decarbonization. By analysing available time series data on fuel use intensity (FUI), fleet size and fish price in 13 European and U.S. bottom trawl fisheries, we find empirical evidence that lower FUI is associated with higher stock abundance. Lower FUI is also observed for catches with lower fish prices and with reductions in fleet size. Results suggest that rebuilding fish stocks by setting and following sustainable harvest limits combined with balancing fishing capacity with resource availability can be one part of a decarbonization strategy. However, economic incentives such as fish price and subsidies are counterproductive. Combined, this suggests that energy use and carbon emissions be considered as key fisheries management objectives. The sparse data availability of fuel use in fisheries also points to the need for standardised collection programs to allow for further research for improved understanding as well as monitoring progress towards societal objectives.

Expert perspectives on exposure-response functions for urban health policy: Lessons from a UBDPolicy workshop - Harry Williams; Zorana Jovanovic Andersen; Hanna Boogaard; Søren Brage; Matthew H.E.M. Browning; Samuel Cai; Xuan Chen; Priyanka deSouza; Angel M. Dzhambov; Benjamin Fenech; Gillian Flower; Francesco Forastiere; et al. (Environmental Research, 2026)

A robust 1K-core marker set for wild germplasm management and targeted pre-breeding of rice: development and applications - Debashree Dalai; Dipti Ranjan Pani; Swayamsiddha Aswita Dhal; Motilal Behera; Tapan Kumar Mondal; Muhammad Azaharudheen TP; Joshitha Vijayan; Deepa Sarkar; Pallavi Ghose; Abhijeet Roy; Kutubuddin A Molla; Anilkumar C; et al. (Theoretical and Applied Genetics, 2026)

Optimized Agrobacterium-mediated CRISPR/Cas9 transformation in soybean through comparative evaluation of cotyledonary node and half-seed explants - Durgeshwari Prabhakar Gadpayale; J. Sushmita; Navita Bansal; Shalini Singh; Ch Prasanna Kumari; C. R. Nagesh; Ranjeet Ranjan Kumar; G. Rama Prashat; Shivani Nagar; Soham Ray; R. Dinesh Kumar; Arun Kumar; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

The teat skin microbiota of organic primiparous dairy cows is dynamic during the transition period - C.J. Dean; T. Ray; F. Peña-Mosca; T.J. Wehri; K. Sharpe; A.M. Antunes; E. Doster; L. Fernandes; V.F. Calles; C. Bauman; B. Heins; P. Pinedo; et al. (Preventive Veterinary Medicine, 2025)

Detection, isolation, and identification of Rhizoctonia theobromae associated with cassava witches’ broom disease in the Philippines - Darwin M. Landicho; Ray Jerome M. Montañez; Vicky S. Manayon; Ma Kristina Yzabelle C. Sendaydiego; Jestoni O. Gaylo; Amor C. Dimayacyac; Ikuo Sato; Daigo Takemoto; Marita S. Pinili; Sotaro Chiba (Physiological and Molecular Plant Pathology, 2025)

Effect of the garlic matrix and inclusion level on in vitro methane production and fermentation - N.F. Sari; S. Stergiadis; P.P. Ray; C. Rymer; L.A. Crompton; K.E. Kliem (Animal Feed Science and Technology, 2025)

Computational NMR enhances metabolomic analysis and sustainability - Matthias Niemitz; Petrus Korhonen; Juuso Lehtivarjo; G. Joseph Ray; David C. Lankin; Charlotte A. Corbett; Shao-Nong Chen; Guido F. Pauli (Phytochemistry Letters, 2025)

Deciphering cGAS-STING signaling: implications for tumor immunity and hepatocellular carcinoma - Harish C. Chandramoorthy; Raed Obaid Saleh; Farag M. A. Altalbawy; Jaafaru Sani Mohammed; Subbulakshmi Ganesan; Mayank Kundlas; J Premkumar; Subhashree Ray; Yasser Fakri Mustafa; Jamal K. Abbas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Seaweed extract-based biostimulants alleviate nutrient stress and enhance productivity and grain quality of wheat through efficient use of fertilizers nutrients under sub-optimal NPK application - Bijan Kumar Mondal; Abir Dey; M. C. Meena; Debarup Das; Archana Singh; Shivani Nagar; Prasenjit Ray; P. K. Upadhyay; Deepak Bamel; Amit Kumar Dash; Krishna Kumar Mourya; Narender Yadava; et al. (Journal of Applied Phycology, 2025)

Complete mitochondrial DNA genome of the Indian Chhattisgarh duck and its phylogenetic analysis - Rajni Kumari; Ratna Prabha; Tirupati Rao Golla; P. K. Ray; Reena Kamal; Jaipal S. Choudhary; Abhay Kumar; Sanjay Kumar; Shanker Dayal; P. C. Chandran; Jyoti Kumar; M. K. Tripathi; et al. (Journal of Genetics, 2025)

The petrology and geochemistry of the Montagna Grande-Monte Gibele trachytic shield volcano (Pantelleria, Italy) - John C. White; Ray Macdonald; Pierangelo Romano; Bogusław Bagiński; Silvio G. Rotolo; Beata Marciniak-Maliszewska; Alessandra Cinquegrani (Geochemistry, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Emulation or Degradation? Evaluating Forest Management Outcomes in Boreal Northeastern Ontario - Jay R. Malcolm; Julee J. Boan; Justina C. Ray (Environmental Management, 2025)

Microbial source tracking in a coastal residential canal system - Nicole C. Powers; Anna Gitter; Nora Bleth; Andrew Johnson; Jacqueline Nicolay; Ray Ayers; Jeffrey W. Turner (Science of The Total Environment, 2025)

Socio-economic impacts and responses of the fishing industry and fishery managers to changes in small pelagic fish distribution and abundance - Felipe J. Quezada-Escalona; Desiree Tommasi; Isaac C. Kaplan; Pierre-Yves Hernvann; Timothy H. Frawley; Dorleta Garcia; Leire Ibaibarriaga; Sonia Sánchez-Maroño; Carryn de Moor; Jennifer Beckensteiner; Amy M. Schueller; Diana Feijó; et al. (Reviews in Fish Biology and Fisheries, 2025)
Small Pelagic Fish (SPF) exhibit large fluctuations in abundance and distribution in response to environmental variability. To maintain the resilience of fishing communities and develop effective and equitable climate adaptation strategies, improved understanding of how the fishing industry responds to spatio-temporal shifts within and across SPF populations is of critical importance. In this paper, we examine the responses of the fishing industry and resource managers to shifts in SPF availability worldwide and identify the resulting socioeconomic impacts. Leveraging SPF case studies from around the globe, we synthesize and compare the social-ecological linkages and feedbacks mediating how SPF fisheries respond to changes in marine ecosystem structure and function associated with (1) spatial shifts in species distribution and habitat availability, (2) ‘boom and bust’ population dynamics, or (3) changes in fish size and quality. Our case studies illustrate multiple paths towards the resilience of small pelagic fisheries and the fishing industry dependent upon them while emphasizing the need for increased coordination and cooperation across sectors and scales as climate change progresses. Drawing from the lessons offered by historical responses, as environmental variability increases, efforts to increase the flexibility and dynamism of SPF harvest portfolios and management strategies, licensing regimes, and international catch and allocation agreements may be required to ensure resource sustainability and human well-being.

Stability analysis and prediction of Bimslope failures using numerical modelling and hybrid meta-heuristic models - Arunava Ray; Gopika C. Atul; Sanjog Chhetri Sapkota; Prasenjit Saha; Sourav Das; Rajesh Rai; Manoj Khandelwal (Natural Hazards, 2025)
Bimsoil slope (Bimslope) or Soil-Rock-Mixture slopes are complex geological formations made up of geotechnically important ‘blocks’ enclosed in a finer-textured ‘matrix.’ These geomaterials possess heterogeneous properties owing to changes in the block and matrix properties that can arise from natural weathering processes or various anthropogenic activities. The present study focuses on the stability analysis of a Bimslope under varying block properties (orientation and volumetric block proportion), matrix type (Loamy sand, Sandy loam, and Silt loam) and matrix water content. The study indicates that the failure of a Bimslope is not governed by only one physical parameter but rather by a critical combination of block properties, matrix type and matrix water content. When the water content (< 25% saturation) and block content (< 25%) are less, the failure is governed by matrix only. With the increase in block content, the failure is governed by block however under fully saturated (100% saturation) conditions, the failure is solely governed by matrix type irrespective of block properties. In addition to that, the data generated using numerical analysis was used to predict the factor of safety using hybridized ensembled methods considering the XGB model and three other novel meta-heuristic algorithms (MHA): political optimization (POA), the Leopard Seal algorithm (LSA), and the Giant Armadillo Algorithm (GAA). It has been found that among all the models, the GAA-XGB algorithm exhibits better results with R 2 and RMSE values as 0.99628, 0.055436 in training and 0.985664, 0.063092 in the testing stage. Furthermore, SHAP-based analysis has been performed to identify the most influential parameters.

Interactions between subpolar and subtropical jet streams lead to extreme rainfall events over the North Indian Subcontinent in June 2013 and July 2023 - Dipanjan Dey; Ligin Joseph; Arkaprava Ray; Robert Marsh; Nikolaos Skliris; Andrew G. Turner; D. C. Ayantika; Parthasarathi Mukhopadhyay; Arun Chakraborty; Sourav Sil (Climate Dynamics, 2025)
North Indian Subcontinent (NIS) is prone to disastrous and life-threatening floods during the summer monsoon period primarily due to its close proximity with the Himalayan foothills. Indian Meteorological Department (IMD) reported that during June 13–19, 2013, the Uttarakhand state in North India experienced a cumulative total of 322 mm rainfall, a 847% weekly departure against the long-term average rainfall (1971–2020) of 34 mm. After a decade, another state in the same region, Himachal Pradesh, received an unprecedented 223 mm of rainfall in just 4 days, viz 7–11 July 2023, a 436% deviation from the cumulative climatological rainfall of 41.6 mm for 4 days (July 7–11). It is shown that the atmospheric water vapor is transported towards NIS by two monsoon low pressure systems during the June 2013 event. In contrast, during the July 2023 flood, the monsoon trough shifted southward, resulting in the moisture transport pathway predominantly over the northern Indian Ocean. In conjunction, it was shown through upper-level air tracing that southward movement of the subpolar jet stream creates a trough in the subtropical jet stream, which intrudes along the western boundary of NIS, leading to upper-level divergence. This pattern was observed in both flood events. By leveraging the mass-conserving nature and unique capability of a Lagrangian tracing model to track atmospheric water backward in time, our novel analysis of the 2023 flood reveals that two evaporative sources near Madagascar and the western Indian Ocean were key contributors, and inland evaporation played a comparatively lesser role as compared to the 2013 case. The Bay of Bengal served primarily as a vapor transport pathway rather than a direct moisture source for both events. This novel Lagrangian approach, which exposes separate drivers of extreme monsoon rainfall, upstream and at lead times of days-weeks, has the potential to be used more extensively and operationally.

Importance of clinopyroxene mineral chemistry as a potential petrogenetic indicator: A case study from gabbroic intrusives from Western Iron Ore Group, Singhbhum Craton, Eastern India - Madhuparna Paul; Biswajit Ghosh; Tomoaki Morishita; Akihiro Tamura; Jyotisankar Ray; C Manikyamba; Suresh C Patel (Journal of Earth System Science, 2025)

Retraction Note: Transgenic rice expressing Allium sativum leaf lectin with enhanced resistance against sap-sucking insect pests - Prasenjit Saha; Pralay Majumder; Indrajit Dutta; Tui Ray; S. C. Roy; Sampa Das (Planta, 2025)

Mineral chemistry-perspective of the Kadavur gabbro-anorthosite Complex, Southern Granulite Terrane of the Indian shield: Implications to its petrogenesis in a ridge-subduction setting - Debaleena Sarkar; Jyotisankar Ray; Rohit Pandey; Moumita Chowdhury; Christian Koeberl; Suresh C. Patel; Desikan Ramakrishnan; Aantarica Chakraborty; Simran Dutta (Lithos, 2025)

Comparing voluntary and government-mandated management measures for meeting sustainable fishing targets - Michael C. Melnychuk; Samantha Lees; Pedro Veiga; Jennifer Rasal; Nicole Baker; Lauren Koerner; Daniel Hively; Hiroyuki Kurota; Carryn L. de Moor; Maite Pons; Pamela M. Mace; Ana M. Parma; et al. (Journal of Environmental Management, 2025)

Molecular Characterization and Seasonal Variation in Expression of HSP70.1 Gene in Gangatiri Cattle and Its Comparison with Buffalo - Shanker Dayal; Birendra Kumar; Rajni Kumari; Jyoti Kumar; Pradeep Kumar Ray; P. C. Chandran; Amitava Dey (Biochemical Genetics, 2025)

Detecting infrastructure hazard potential change by SAR techniques on postseismic surface deformation: A case study of 2016 Meinong earthquake in southwestern Taiwan - Chih-Heng Lu; Ray C. Chuang; Ping-Chen Chiang; Jiun-Yee Yen; Kuo-En Ching; Yue-Gau Chen (Engineering Geology, 2025)

Evaluation of easterly wave disturbances over the tropical South Atlantic in CMIP6 models - Lucas C. V. Cavalcante; Helber B. Gomes; Kevin Hodges; Pallav Ray; Dirceu L. Herdies; Henrique M. J. Barbosa; Weber A. Gonçalves; Maria Cristina L. Silva; José Ivaldo B. de Brito; João Pedro G. Nobre; Matheus J. A. Lyra; Hakki Baltaci (Climate Dynamics, 2025)

Lactic acid bacteria in the functional food industry: biotechnological properties and potential applications - Md Minhajul Abedin; Rounak Chourasia; Loreni Chiring Phukon; Puja Sarkar; Ramesh C. Ray; Sudhir P. Singh; Amit Kumar Rai (Critical Reviews in Food Science and Nutrition, 2024)

Electrocatalytic synergies of melt-quenched Ni-Sn-Se-Te nanoalloy for direct seawater electrolysis - John D. Rodney; Sindhur Joshi; Subhasmita Ray; Lavanya Rao; S. Deepapriya; Karel Carva; Badekai Ramachandra Bhat; N.K. Udayashankar; Suresh Perumal; Sadhana Katlakunta; C. Justin Raj; Byung Chul Kim (Chemical Engineering Journal, 2024)

Metal cation and crystal lattice water molecule stabilized highly mesoporous manganese oxide network for excellent durable electrode in sodium-ion storage - Ramu Manikandan; C. Justin Raj; Hyun Jung; John D. Rodney; Subhasmita Ray; Antonysamy Dennyson Savariraj; Periyasamy Sivakumar; K. Karuppasamy; Byung Chul Kim; Jae-Min Oh (Chemical Engineering Journal, 2024)

A Perspective on Evaluating Life Stage Differences in Drug Dosages for Drug Labeling and Instructions - Tianshu Gu; Guiying Wang; Edwin J. C. van den Oord; Emanuel Goldman; Chengyuan Yang; Ning Xie; Lan Yao; Cong-Yi Wang; Monica Jablonski; Kunal Ray; Fengxia Liu; Wensen Pan; et al. (The AAPS Journal, 2024)

Mixed-Method Heat Acclimation Induces Heat Adaptations in International Triathletes Without Training Modification - Carl A. James; Ashley G. B. Willmott; C. W. Daniel Lee; T. K. Gabriel Pun; Ray Tai; Oliver R. Gibson (Journal of Science in Sport and Exercise, 2024)
Purpose Heat acclimation (HA) kinetics often necessitates that the intervention is conducted in the weeks immediately preceding athletic competitions, potentially interfering with a training taper. Therefore, we investigated the efficacy of a mixed-method HA protocol, superimposed over planned external training loads, during the 3-weeks prior to the 2022 U23 World Triathlon Championships. Methods Six international triathletes completed 8 pre-competition HA sessions (5 active: running/cycling, 3 passive: hot water immersion [HWI]), across 2-weeks. Outdoor high-intensity training sessions were followed by 30–60 min HWI, whilst low-intensity cycling/running sessions were completed in a hot, humid environmental chamber. To assess heat adaptations, participants completed three 25 min heat stress tests (HST) involving iso-speed treadmill running (session 1 = HST1, session 5 = HST2, and session 8 = HST3). Physiological, haematological and wellbeing monitoring were conducted throughout HA. Results Reduced heart rate (~ − 6 beats/min) was observed within HST3 ( P = 0.01, η p 2 = 0.64), versus HST1 and HST2. No changes in core temperature were observed across HSTs ( P = 0.055 , η p 2 = 0.44). Sweat sodium concentration was lower by HST2 at the arm (− 23 ± 16 mmol/L, P = 0.02) and back (− 27 ± 17 mmol/L, P = 0.01). White blood cell count reduced from baseline to the end of HA ( P = 0.02, η p 2 = 0.27), but no changes were found in any other haematological markers (all P > 0.05). Perceptual wellbeing measures did not change across HA (all P > 0.05). Conclusion By HST3, seven prior mixed-method HA sessions improved markers of heat adaptation (exercising HR and sweat concentration) within international triathletes. Mixed-method HA may be implemented without modifying training load, with no apparent detrimental effects on athlete health or training stress markers.

Reconstructing 120 years of climate change impacts on Joshua tree flowering - Jeremy B. Yoder; Ana Karina Andrade; Lesley A. DeFalco; Todd C. Esque; Colin J. Carlson; Daniel F. Shryock; Ray Yeager; Christopher I. Smith (Ecology Letters, 2024)
Quantifying how global change impacts wild populations remains challenging, especially for species poorly represented by systematic datasets. Here, we infer climate change effects on masting by Joshua trees ( Yucca brevifolia and Y. jaegeriana ), keystone perennials of the Mojave Desert, from 15 years of crowdsourced observations. We annotated phenophase in 10,212 geo‐referenced images of Joshua trees on the iNaturalist crowdsourcing platform, and used them to train machine learning models predicting flowering from annual weather records. Hindcasting to 1900 with a trained model successfully recovers flowering events in independent historical records and reveals a slightly rising frequency of conditions supporting flowering since the early 20th Century. This reflects increased variation in annual precipitation, which drives masting events in wet years—but also increasing temperatures and drought stress, which may have net negative impacts on recruitment. Our findings reaffirm the value of crowdsourcing for understanding climate change impacts on biodiversity.

Effects of increasing soil moisture on Antarctic desert microbial ecosystems - Eden Zhang; Sin Yin Wong; Paul Czechowski; Aleks Terauds; Angelique E. Ray; Nicole Benaud; Devan S. Chelliah; Daniel Wilkins; Kate Montgomery; Belinda C. Ferrari (Conservation Biology, 2024)
Overgeneralization and a lack of baseline data for microorganisms in high‐latitude environments have restricted the understanding of the microbial response to climate change, which is needed to establish Antarctic conservation frameworks. To bridge this gap, we examined over 17,000 sequence variants of bacteria and microeukarya across the hyperarid Vestfold Hills and Windmill Islands regions of eastern Antarctica. Using an extended gradient forest model, we quantified multispecies response to variations along 79 edaphic gradients to explore the effects of change and wind‐driven dispersal on community dynamics under projected warming trends. We also analyzed a second set of soil community data from the Windmill Islands to test our predictions of major environmental tipping points. Soil moisture was the most robust predictor for shaping the regional soil microbiome; the highest rates of compositional turnover occurred at 10–12% soil moisture threshold for photoautotrophs, such as Cyanobacteria , Chlorophyta , and Ochrophyta . Dust profiles revealed a high dispersal propensity for Chlamydomonas , a microalga, and higher biomass was detected at trafficked research stations. This could signal the potential for algal blooms and increased nonendemic species dispersal as human activities increase in the region. Predicted increases in moisture availability on the Windmill Islands were accompanied by high photoautotroph abundances. Abundances of rare oligotrophic taxa, such as Eremiobacterota and Candidatus Dormibacterota, which play a crucial role in atmospheric chemosynthesis, declined over time. That photosynthetic taxa increased as soil moisture increased under a warming scenario suggests the potential for competition between primary production strategies and thus a more biotically driven ecosystem should the climate become milder. Better understanding of environmental triggers will aid conservation efforts, and it is crucial that long‐term monitoring of our study sites be established for the protection of Antarctic desert ecosystems. Furthermore, the successful implementation of an improved gradient forest model presents an exciting opportunity to broaden its use on microbial systems globally.

Editorial Expression of Concern: Transgenic rice expressing Allium sativum leaf lectin with enhanced resistance against sap-sucking insect pests - Prasenjit Saha; Pralay Majumder; Indrajit Dutta; Tui Ray; S. C. Roy; Sampa Das (Planta, 2024)

Salt type, sugar addition, and system type in intensive RAS for Pacific white shrimp (Litopenaeus vannamei) production - Shrijan Bajracharya; Jill C. Fisk; Leo J. Fleckenstein; Andrew J. Ray (Aquaculture, 2024)

Single-crystal 40Ar/39Ar dating of the Montagna Grande-Monte Gibele trachytic shield volcano, Pantelleria (Strait of Sicily rift zone), Italy - John C. White; Daniel P. Miggins; Ray Macdonald (Geochemistry, 2024)

Piezocatalytic property of PVDF/Graphene self-assembling piezoelectric membrane for environmental remediation - Tsung-Han Huang; Franz Kenneth C. Espino; Xin-Yuan Tian; Januar Widakdo; Hannah Faye M. Austria; Owen Setiawan; Wei-Song Hung; Kristopher Ray S. Pamintuan; Rhoda B. Leron; Ching-Yuan Chang; Alvin R. Caparanga; Kueir-Rarn Lee; et al. (Chemical Engineering Journal, 2024)

Investigating impacts of the mycothiazole chemotype as a chemical probe for the study of mitochondrial function and aging - Naibedya Dutta; Joe A. Gerke; Sofia F. Odron; Joseph D. Morris; Adam Hruby; Juri Kim; Toni Castro Torres; Sarah J. Shemtov; Jacqueline G. Clarke; Michelle C. Chang; Hooriya Shaghasi; Marissa N. Ray; et al. (GeroScience, 2024)
Small molecule inhibitors of the mitochondrial electron transport chain (ETC) hold significant promise to provide valuable insights to the field of mitochondrial research and aging biology. In this study, we investigated two molecules: mycothiazole (MTZ) - from the marine sponge C. mycofijiensis and its more stable semisynthetic analog 8- O -acetylmycothiazole (8-OAc) as potent and selective chemical probes based on their high efficiency to inhibit ETC complex I function. Similar to rotenone (Rote), MTZ, a newly employed ETC complex I inhibitor, exhibited higher cytotoxicity against cancer cell lines compared to certain non-cancer cell lines. Interestingly, 8-OAc demonstrated greater selectivity for cancer cells when compared to both MTZ and Rote, which has promising potential for anticancer therapeutic development. Furthermore, in vivo experiments with these small molecules utilizing a C. elegans model demonstrate their unexplored potential to investigate aging studies. We observed that both molecules have the ability to induce a mitochondria-specific unfolded protein response (UPR MT ) pathway, that extends lifespan of worms when applied in their adult stage. We also found that these two molecules employ different pathways to extend lifespan in worms. Whereas MTZ utilizes the transcription factors ATFS-1 and HSF1, which are involved in the UPR MT and heat shock response (HSR) pathways respectively, 8-OAc only required HSF1 and not ATFS-1 to mediate its effects. This observation underscores the value of applying stable, potent, and selective next generation chemical probes to elucidate an important insight into the functional roles of various protein subunits of ETC complexes and their regulatory mechanisms associated with aging. Graphical Abstract

The development of early farming diets and population change in the Maya region and their climate context - Erin E. Ray; Nadia C. Neff; Paige Lynch; Jose Mes; Matthew S. Lachniet; Douglas J. Kennett; Keith M. Prufer (Quaternary International, 2024)

Identification of QTLs for symbiotic nitrogen fixation and related traits in a soybean recombinant inbred line population - C. Bennet Krueger; Jeffery D. Ray; James R. Smith; Arun Prabhu Dhanapal; Muhammad Arifuzzaman; Fei Gao; Felix B. Fritschi (Theoretical and Applied Genetics, 2024)

Lessons from COP15 on effective scientific engagement in biodiversity policy processes - Carlos Carroll; Sean Hoban; Justina C. Ray (Conservation Biology, 2024)
The Kunming–Montreal Global Biodiversity Framework was adopted by parties to the Convention on Biological Diversity in December 2022. The aftermath of these negotiations provides an opportunity to draw lessons as to how ecological and evolutionary science can more effectively inform policy. We examined key challenges that limit effective engagement by scientists in the biodiversity policy process, drawing parallels with analogous challenges within global climate negotiations. Biodiversity is multifaceted, yet represents only one framing for nature's contributions to people, complicating the nexus between evidence and values in development of the framework's targets. Processes generating biodiversity and driving its loss are multiscalar, challenging development of an evidence base for globally standardized targets. We illustrated these challenges by contrasting development of 2 key elements of the framework. The genetic diversity element of the framework's target 4 is directly related to the framework's primary goals, but its complexity required development of novel engagement skills. The target for protected areas was easily communicated but more indirectly related to biodiversity outcomes; evidence from ecological and social science was essential to communicating the context and limitations of this relationship. Scientists can strengthen the effectiveness of global agreements and address challenges arising from complexity, scaling, capacity limitations, and the interplay of science and values, if they can prioritize communication, consensus‐building, and networking skills and engage throughout the process, from development of an evidence base to implementation.

Metagenomics untangles potential adaptations of Antarctic endolithic bacteria at the fringe of habitability - Claudia Coleine; Davide Albanese; Angelique E. Ray; Manuel Delgado-Baquerizo; Jason E. Stajich; Timothy J. Williams; Stefano Larsen; Susannah Tringe; Christa Pennacchio; Belinda C. Ferrari; Claudio Donati; Laura Selbmann (Science of The Total Environment, 2024)

Quota use in mixed‐stock fisheries - William A. Karp; Michael C. Melnychuk; Robyn E. Forrest; Lorne Richard Little; Kristin McQuaw; Chad Demarest; Ray Hilborn; Nicole Baker; Brian Mose; Bruce Turris; Ernesto Penas Lado (Fish and Fisheries, 2024)
Although most fisheries assessment and management focuses on the status of individual stocks, and regulations are commonly established as single‐species total allowable catch limits (TACs), much of the catch from global fisheries comes from mixed‐stock fisheries where species cannot be harvested separately. We show that in some fisheries where TAC and catch of demersal fish stocks are tracked, the average fraction of TAC harvested ranges from 21% to 68% overall and is declining. This is, in part, related to efforts to protect all species from overfishing, leading to ‘choke species’, which limit fishing pressure on other target species. While some choke species arise from a mix of low and high‐productivity species, others result from allocation processes, which can be aggravated by shifting distributions due to climate change. Underutilization of TACs can also result from market limitations, low value of individual species, undercapacity or management measures. Proposed methods for increasing long‐term yield require species to be managed in stock groups, or allowing the abundance of some stocks to fall below target reference points. We suggest that the observed low and declining aggregate harvests are due, primarily, to the focus on single‐stock sustainability measures, rather than performance of the fisheries in relation to potential overall yield. While there is a growing consensus that single‐species management should be replaced by an ecosystem‐based approach, this will require clear legislative directives regarding management of the trade‐offs involved. Time series considered in this analysis do not extend beyond 2019.

Analysis of localized features during wet and dry rainfall episodes over southern tip of India - E. A. Resmi; B. Preethi; R. S. Ajayamohan; Pallav Ray; C. K. Unnikrishnan; S. Nita; R. K. Sumesh; J. Dharmadas (International Journal of Climatology, 2023)
The large spatial and temporal variability of wet and dry spells of the Indian Summer Monsoon (ISM) poses the great challenge in understanding and predicting monsoonal rainfall. This challenge is further exacerbated over smaller regions, such as the southern tip of India, which receives the first spell of ISM rainfall. In this study, the characteristic features and possible precursors for wet and dry spells of rainfall over the southern tip of India are investigated. We also explore the variability in monsoon low‐level jet (LLJ) in relation to wet and dry spells over a coastal station Thiruvananthapuram (8.48°N, 76.95°E) in southwest India using in situ observations and other ancillary datasets. The results show that a wet spell spanning 3–4 days contributes about 30% of seasonal rainfall. Wet spells are characterized by westerly wind anomaly in the southern tip of India and easterly wind anomaly in northern India, leading to anomalous cyclonic vorticity over the Indian subcontinent. The opposite happens during dry spells. These characteristics are prominent from 2 days prior to the initiation of the spells, suggesting they may be used as precursors for forecasting wet and dry spells over Thiruvananthapuram. Analysis of low‐ to mid‐tropospheric (2 and 4 km) humidity reveals significant moistening (drying) during wet (dry) spells. Yet, both wet and dry spells experience humid (>80%) boundary layer. The differences in mid‐level humidity and thermodynamical structures between wet and dry spells seem to contribute to distinct rainfall characteristics over the southern tip of India. These results indicate that the use of in situ observations along with large‐scale reanalysis datasets may provide valuable information on the precursors for wet and dry spells over the southern tip of India, which can help both in regional‐ and city‐level planning and management of water resources.

The Ontology of Biological Attributes (OBA)—computational traits for the life sciences - Ray Stefancsik; James P. Balhoff; Meghan A. Balk; Robyn L. Ball; Susan M. Bello; Anita R. Caron; Elissa J. Chesler; Vinicius de Souza; Sarah Gehrke; Melissa Haendel; Laura W. Harris; Nomi L. Harris; et al. (Mammalian Genome, 2023)
Existing phenotype ontologies were originally developed to represent phenotypes that manifest as a character state in relation to a wild-type or other reference. However, these do not include the phenotypic trait or attribute categories required for the annotation of genome-wide association studies (GWAS), Quantitative Trait Loci (QTL) mappings or any population-focussed measurable trait data. The integration of trait and biological attribute information with an ever increasing body of chemical, environmental and biological data greatly facilitates computational analyses and it is also highly relevant to biomedical and clinical applications. The Ontology of Biological Attributes (OBA) is a formalised, species-independent collection of interoperable phenotypic trait categories that is intended to fulfil a data integration role. OBA is a standardised representational framework for observable attributes that are characteristics of biological entities, organisms, or parts of organisms. OBA has a modular design which provides several benefits for users and data integrators, including an automated and meaningful classification of trait terms computed on the basis of logical inferences drawn from domain-specific ontologies for cells, anatomical and other relevant entities. The logical axioms in OBA also provide a previously missing bridge that can computationally link Mendelian phenotypes with GWAS and quantitative traits. The term components in OBA provide semantic links and enable knowledge and data integration across specialised research community boundaries, thereby breaking silos.

Characterizing state‐managed and unmanaged fisheries in coastal marine states and territories of the United States - Michael C. Melnychuk; Charmane E. Ashbrook; Richard J. Bell; Lyall Bellquist; Kate Kauer; Jono R. Wilson; Ray Hilborn; Jay Odell (Fish and Fisheries, 2023)
The status of federally managed fisheries in the United States is well monitored, but the condition of other marine fisheries, whether state‐managed, territory‐managed or unmanaged, is less understood and often unknown. We used expert surveys to characterize the management systems of non‐federally managed fisheries in US coastal marine states and overseas territories. For 311 fisheries, we estimated an overall Fisheries Management Index (FMI) and a qualitative stock status score. These measures were positively correlated, and while a wide range of research, management, enforcement and socioeconomic criteria were partially met (FMI ≥ 0.5) for 66% of fisheries, stock status was considered as partially acceptable (score ≥ 0.5) for only 45% of fisheries and acceptable (score = 1) for only 16% of fisheries. Higher FMI was typically observed in fisheries with greater commercial landed weight, value, or greater recreational catches. Fisheries from continental states had higher FMI than those from overseas territories. Invertebrates and diadromous fish species had higher FMI on average compared to those of marine fishes. Extrapolating results for surveyed fisheries to nearly 2000 non‐federally managed US fisheries while stratifying by state and importance designation (based on commercial, recreational, cultural or ecological importance), we estimate a mean overall FMI of 0.48, and estimate that only 19% of fisheries have a reliable estimate of stock status available; both measures are lower than similar estimates for federally managed fisheries. Funding or capacity constraints and information or data limitations were identified as common challenges faced by state agencies in managing fisheries under their jurisdiction.

Impact of relative humidity and temperature oscillations mimicking authentic storage during shipping on whey proteins powders properties - J. Burgain; G. Francius; L. Cvetkovska; C. Paris; M. Alexander; C. Ray; S. El-Kirat-Chatel; C. Gaiani (Food Structure, 2023)

Spatial and temporal variability in summertime dissolved carbon dioxide and methane in temperate ponds and shallow lakes - Nicholas E. Ray; Meredith A. Holgerson; Mikkel Rene Andersen; Jānis Bikše; Lauren E. Bortolotti; Martyn Futter; Ilga Kokorīte; Alan Law; Cory McDonald; Jorrit P. Mesman; Mike Peacock; David C. Richardson; et al. (Limnology and Oceanography, 2023)
Small waterbodies have potentially high greenhouse gas emissions relative to their small footprint on the landscape, although there is high uncertainty in model estimates. Scaling their carbon dioxide (CO 2 ) and methane (CH 4 ) exchange with the atmosphere remains challenging due to an incomplete understanding and characterization of spatial and temporal variability in CO 2 and CH 4 . Here, we measured partial pressures of CO 2 ( p CO 2 ) and CH 4 ( p CH 4 ) across 30 ponds and shallow lakes during summer in temperate regions of Europe and North America. We sampled each waterbody in three locations at three times during the growing season, and tested which physical, chemical, and biological characteristics related to the means and variability of p CO 2 and p CH 4 in space and time. Summer means of p CO 2 and p CH 4 were inversely related to waterbody size and positively related to floating vegetative cover; p CO 2 was also positively related to dissolved phosphorus. Temporal variability in partial pressure in both gases weas greater than spatial variability. Although sampling on a single date was likely to misestimate mean seasonal p CO 2 by up to 26%, mean seasonal p CH 4 could be misestimated by up to 64.5%. Shallower systems displayed the most temporal variability in p CH 4 and waterbodies with more vegetation cover had lower temporal variability. Inland waters remain one of the most uncertain components of the global carbon budget; understanding spatial and temporal variability will ultimately help us to constrain our estimates and inform research priorities.

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

Cytogenetic Diversity in Scilloideae (Asparagaceae): a Comprehensive Recollection and Exploration of Karyo-Evolutionary Trends - Sayantani Nath; Sayantika Sarkar; Sayali D. Patil; Partha Sarathi Saha; Manoj M. Lekhak; Sudipta Ray; Satyawada Rama Rao; S. R. Yadav; R. C. Verma; Manoj K. Dhar; S. N. Raina; Sumita Jha (The Botanical Review, 2023)

Critical Market Tipping Points for High-Grade White Oak Inventory Decline in the Central Hardwood Region of the United States - Gaurav Dhungel; David Rossi; Jesse D Henderson; Robert C Abt; Ray Sheffield; Justin Baker (Journal of Forestry, 2023)
This study expands the spatial scope of the Subregional Timber Supply (SRTS) model to include states in the central hardwood region and examine critical market tipping points of high-grade (large diameter) white oak under a set of illustrative scheduled demand scenarios. In light of the growing concern for future white oak timber supply, we illustrate the sensitivity of future inventory tipping points to market structure and price responsiveness. Particularly, we examined the importance of market demand parameters, including growth rates for product demand and supply/demand elasticities, in influencing future inventory trajectories in different subregions over the projection horizon. Results of this study indicate that more elastic demand and more inelastic supply response concomitantly defers the time before inventory culminates. This modeling framework shows promise in examining key ecological, climatic, and economic interrelationships that will drive future resource changes.

The effects of stocking density and artifical substrate on production of pacific white shrimp Litopenaeus vannamei and water quality dynamics in greenhouse-based biofloc systems - Nathan A. Kring; Leo J. Fleckenstein; Thomas W. Tierney; Jill C. Fisk; Benjamin C. Lawson; Andrew J. Ray (Aquacultural Engineering, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Probabilistic inversion of audio-frequency magnetotelluric data and application to cover thickness estimation for mineral exploration in Australia - Wenping Jiang; Ross C. Brodie; Jingming Duan; Ian Roach; Neil Symington; Anandaroop Ray; James Goodwin (Journal of Applied Geophysics, 2023)

Combining Community Wastewater Genomic Surveillance with State Clinical Surveillance: A Framework for SARS-CoV-2 Public Health Practice - Ted Smith; Rochelle H. Holm; Ray Yeager; Joseph B. Moore; Eric C. Rouchka; Kevin J. Sokoloski; Erin M. Elliott; Daymond Talley; Vaneet Arora; Sarah Moyer; Aruni Bhatnagar (Food and Environmental Virology, 2022)
This study aimed to develop a framework for combining community wastewater surveillance with state clinical surveillance for the confirmation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants within the community and to provide recommendations on how to expand on such research and apply the findings in public health responses. Wastewater samples were collected weekly from 17 geographically resolved locations in Louisville/Jefferson County, Kentucky (USA), from February 10 to December 13, 2021. Genomic surveillance and quantitative reverse transcription PCR (RT-qPCR) platforms were used to screen for SARS-CoV-2 in wastewater, and state clinical surveillance was used for confirmation. The study results highlighted an increased epidemiological value of combining community wastewater genomic surveillance and RT-qPCR with conventional case-auditing methods. The spatial scale and temporal frequency of wastewater sampling provided promising sensitivity and specificity for gaining public health screening insights about SARS-CoV-2 emergence, seeding, and spread in communities. Improved national surveillance systems are needed against future pathogens and variants, and wastewater-based genomic surveillance exhibits great potential when coupled with clinical testing. This paper presents evidence that complementary wastewater and clinical testing are cost-effectively enhanced when used in combination, as they provide a strong tool for a joint public health framework. Future pathogens of interest may be examined in either a targeted fashion or using a more global approach where all pathogens are monitored. This study has also provided novel insights developed from evidence-based public health practices.

An explanation for unexpected population crashes in a constant environment - Evan C. Johnson; Alan Hastings; Chris Ray (Ecology Letters, 2022)
Unexpected population crashes are an important feature of natural systems, yet many observed crashes have not been explained. Two difficulties in explaining population crashes are their relative rarity and the multi‐causal nature of ecological systems. We approach this issue with experimental microcosms, with large numbers of replicates of red flour beetle populations ( Tribolium castaneum ). We determined that population crashes are caused by an interaction between stochasticity and successive episodes of density dependence: demographic stochasticity in oviposition rates occasionally produces a high density of eggs; so high that there are insufficient flour resources for subsequent larvae. This mechanism can explain unexpected population crashes in more general settings: stochasticity ‘pushes’ population into a regime where density dependence is severely overcompensatory. The interaction between nonlinearity and stochasticity also produces chaotic population dynamics and a double‐humped one‐generation population map, suggesting further possibilities for unexpected behaviour in a range of systems. We discuss the generality of our proposed mechanism, which could potentially account for previously inexplicable population crashes.

Recent trends in abundance and fishing pressure of agency‐assessed small pelagic fish stocks - Ray Hilborn; Claudio C. Buratti; Erich Díaz Acuña; Daniel Hively; Jeppe Kolding; Hiroyuki Kurota; Nicole Baker; Pamela M. Mace; Carryn L. de Moor; Soyoka Muko; Giacomo Chato Osio; Ana M. Parma; et al. (Fish and Fisheries, 2022)
Small pelagic fishes are used for human consumption, fishmeal and fish oil. They constitute 25% of global fish catch and have been of considerable conservation concern because of their intermediate position in aquatic food webs, often being a dominant dietary component of marine predators. This paper provides an overview of trends in abundance and fishing pressure on small pelagic fish stocks from single‐species scientific assessments that constitute 60% of global small pelagic catch. While most individual stocks have exhibited wide variability in abundance (typical of small pelagics compared with other fish taxa), across stocks there has been remarkable stability in average fishing pressure and biomass since 1970. On average, since 1970, the biomass of assessed small pelagic stocks is estimated to have been slightly above the biomass that would produce maximum sustainable yield, but estimation of this quantity for highly fluctuating stocks is quite uncertain. There were significant differences among assessed regions, with the Mediterranean and Black Sea of greatest concern for high and growing fishing pressure. The 40% of global small pelagic fish catch not covered by single‐species quantitative stock assessments since 1970 comes largely from Asia, where catches have continued to increase. At regional levels, the average abundance of assessed small pelagic fish is largely unrelated to average fishing pressure, which we argue results both from the portfolio effect, where numerous stocks fluctuate with little correlation in abundance, and from the short life span of small pelagics coupled with recruitment largely independent of spawning abundance.

Olivine decadence of continental flood basalts in the light of recent experiments: A case study from Khandwa, Eastern Deccan Volcanic Province - Payel Dey; Jyotisankar Ray; Janisar M Sheikh; Suresh C Patel; Christian Koeberl; Simran Dutta (Journal of Earth System Science, 2022)

Insights into petrogenetic processes from a part of the Eastern Deccan Volcanic Province, India, using cluster analyses of mineralo-chemical data - Payel Dey; Jyotisankar Ray; Janisar M Sheikh; Suresh C Patel; Christian Koeberl; Avipsha Chakraborty (Journal of Earth System Science, 2022)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Methionol, a Sulfur-Containing Pheromone Component from the North American Cerambycid Beetle Knulliana cincta cincta - Marlin E. Rice; Lawrence M. Hanks; Sean Halloran; Judith A. Mongold-Diers; Anna C. Grommes; Robert F. Mitchell; Ann M. Ray; Jocelyn G. Millar (Journal of Chemical Ecology, 2022)

Area‐based management of blue water fisheries: Current knowledge and research needs - Ray Hilborn; Vera N. Agostini; Milani Chaloupka; Serge M. Garcia; Leah R. Gerber; Eric Gilman; Quentin Hanich; Amber Himes‐Cornell; Alistair J. Hobday; David Itano; Michel J. Kaiser; Hilario Murua; et al. (Fish and Fisheries, 2022)
The pelagic fisheries beyond the continental shelves are currently managed with a range of tools largely based on regulating effort or target catch. These tools comprise both static and dynamic area‐based approaches to include gear limitations, closed areas and bycatch limits. There are increasing calls for additional area‐based interventions, particularly expansion of marine protected areas, with many now advocating closing 30% of the oceans to fishing. In this paper, we review the objectives, methods and successes of area‐based management of blue water fisheries across objectives related to food production and environmental, social and economic impacts. We also consider the methods used to evaluate the performance of area‐based regulations and provide a summary of the relative quality of evidence from alternative evaluation approaches. We found that few area‐based approaches have been rigorously evaluated, and that it is often difficult to obtain requisite observational data to define a counterfactual to infer any causal effect for such evaluation. Management agencies have been relatively successful at maintaining important commercial species at or near their target abundance, but success at meeting ecological or social goals is less clear. The high mobility of both target and bycatch species generally reduces the effectiveness of area‐based management, and shifting distributions due to climate change suggest that adaptive rather than static approaches will be preferred. We prioritize research and management actions that would make area‐based management more effective.

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Stem Region of tRNA Genes Favors Transition Substitution Towards Keto Bases in Bacteria - Piyali Sen; Ruksana Aziz; Ramesh C. Deka; Edward J. Feil; Suvendra Kumar Ray; Siddhartha Sankar Satapathy (Journal of Molecular Evolution, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Large‐scale genome sampling reveals unique immunity and metabolic adaptations in bats - Diana D. Moreno Santillán; Tanya M. Lama; Yocelyn T. Gutierrez Guerrero; Alexis M. Brown; Paul Donat; Huabin Zhao; Stephen J. Rossiter; Laurel R. Yohe; Joshua H. Potter; Emma C. Teeling; Sonja C. Vernes; Kalina T. J. Davies; et al. (Molecular Ecology, 2021)
Comprising more than 1,400 species, bats possess adaptations unique among mammals including powered flight, unexpected longevity, and extraordinary immunity. Some of the molecular mechanisms underlying these unique adaptations includes DNA repair, metabolism and immunity. However, analyses have been limited to a few divergent lineages, reducing the scope of inferences on gene family evolution across the Order Chiroptera. We conducted an exhaustive comparative genomic study of 37 bat species, one generated in this study, encompassing a large number of lineages, with a particular emphasis on multi‐gene family evolution across immune and metabolic genes. In agreement with previous analyses, we found lineage‐specific expansions of the APOBEC3 and MHC‐I gene families, and loss of the proinflammatory PYHIN gene family. We inferred more than 1,000 gene losses unique to bats, including genes involved in the regulation of inflammasome pathways such as epithelial defence receptors, the natural killer gene complex and the interferon‐gamma induced pathway. Gene set enrichment analyses revealed genes lost in bats are involved in defence response against pathogen‐associated molecular patterns and damage‐associated molecular patterns. Gene family evolution and selection analyses indicate bats have evolved fundamental functional differences compared to other mammals in both innate and adaptive immune system, with the potential to enhance antiviral immune response while dampening inflammatory signalling. In addition, metabolic genes have experienced repeated expansions related to convergent shifts to plant‐based diets. Our analyses support the hypothesis that, in tandem with flight, ancestral bats had evolved a unique set of immune adaptations whose functional implications remain to be explored.

Dissolved and particulate carbon export from a tropical mangrove‐dominated riverine system - Raghab Ray; Toshihiro Miyajima; Atsushi Watanabe; Masaya Yoshikai; Charissa M. Ferrera; Iris Orizar; Takashi Nakamura; Maria Lourdes San Diego‐McGlone; Eugene C. Herrera; Kazuo Nadaoka (Limnology and Oceanography, 2021)
Despite being a major component in the mangrove carbon (blue carbon) budget, “outwelling” flux (or export to the sea) has gained little attention relative to other biogeochemical fluxes and reservoir carbon stock estimations. This study aims to estimate lateral exchange fluxes of dissolved and particulate organic carbon (DOC, POC) and dissolved inorganic carbon (DIC) from the watershed through a microtidal mangrove‐dominated estuary to the coastal sea in Panay Island, Philippines. Along the estuarine transect, consistent addition of DOC, DIC, and POC at higher salinities were attributed to mangrove organic matter input. Upstream groundwater input (carbonate weathering) and downstream mangrove organic matter decomposition (possibly sulfate reduction) were the main controls on DIC. DOC corresponded to relatively pure mangrove sources in creek water, while POC was a mixture of detrital and algal organic matter. The mangrove system acted as net exporter of carbon to the sea in both dry and wet seasons. From short‐term observations, outwelling fluxes of mangrove‐derived DOC, DIC, and POC contributed 27–53%, 8–31%, and 42%, respectively, to their estuarine outflow. Unlike other studies, such low percentage for DIC might result from other external nonmangrove input (e.g., watershed carbonate weathering). Overall estuarine carbon flux was dominated by DIC (90–95%) with only minor contribution from DOC. The approach utilized in this study to estimate lateral carbon flux specific to a small mangrove setting can be useful in delineating blue carbon budgets that avoid geographical and methodological biases.

A Review of the Opportunities and Challenges for Using Remote Sensing for Management of Surface-Canopy Forming Kelps - Kyle C. Cavanaugh; Tom Bell; Maycira Costa; Norah E. Eddy; Lianna Gendall; Mary G. Gleason; Margot Hessing-Lewis; Rebecca Martone; Meredith McPherson; Ondine Pontier; Luba Reshitnyk; Rodrigo Beas-Luna; et al. (Frontiers in Marine Science, 2021)
Surface-canopy forming kelps provide the foundation for ecosystems that are ecologically, culturally, and economically important. However, these kelp forests are naturally dynamic systems that are also threatened by a range of global and local pressures. As a result, there is a need for tools that enable managers to reliably track changes in their distribution, abundance, and health in a timely manner. Remote sensing data availability has increased dramatically in recent years and this data represents a valuable tool for monitoring surface-canopy forming kelps. However, the choice of remote sensing data and analytic approach must be properly matched to management objectives and tailored to the physical and biological characteristics of the region of interest. This review identifies remote sensing datasets and analyses best suited to address different management needs and environmental settings using case studies from the west coast of North America. We highlight the importance of integrating different datasets and approaches to facilitate comparisons across regions and promote coordination of management strategies.

Breeding latitude is associated with the timing of nesting and migration around the annual calendar among Purple Martin (Progne subis) populations - L. R. Neufeld; S. Muthukumarana; J. D. Fischer; J. D. Ray; J. Siegrist; K. C. Fraser (Journal of Ornithology, 2021)

Global status of groundfish stocks - Ray Hilborn; Daniel J. Hively; Nicole Baker Loke; Carryn L. de Moor; Hiroyuki Kurota; Johannes N. Kathena; Pamela M. Mace; Cóilín Minto; Ana M. Parma; Juan‐Carlos Quiroz; Michael C. Melnychuk (Fish and Fisheries, 2021)
We review the status of groundfish stocks using published scientific assessments for 349 individual stocks constituting 90% of global groundfish catch. Overall, average stock abundance is increasing and is currently above the level that would produce maximum sustainable yield (MSY). Fishing pressure for cod‐like fishes (Gadiformes) and flatfishes (Pleuronectiformes) was, for several decades, on average well above levels associated with MSY, but is now at or below the level expected to produce MSY. In contrast, fishing pressure for rockfishes (Scorpaeniformes) decreased from near MSY‐related levels in the mid‐1990s, and since the mid‐2000s has remained on average at only one third of MSY‐related levels. Regions with the most depressed groundfish stocks are the Northwest Atlantic and the Pacific coast of South America, while stocks from the Northeast and Eastern Central Pacific, Northeast Atlantic, Southeast Atlantic and Southwest Pacific tend to have greatest average abundance relative to MSY‐based reference points. In the most recent year available for each stock, the catch was only 61% of MSY. Equilibrium yield curves indicate that 76% of global potential groundfish yield could be achieved using current estimates of fishing pressure. 15% of this is lost by excess fishing pressure, 67% results from lower than optimal fishing pressure on healthy stocks and 18% is lost from stocks currently overfished but rebuilding. Thus, there is modest opportunity to increase catch of global groundfish fisheries by reducing overfishing on some stocks, but more by increasing harvest on others. However, there may be other reasons not to fully exploit these stocks.

Maximizing the effectiveness of national commitments to protected area expansion for conserving biodiversity and ecosystem carbon under climate change - Carlos Carroll; Justina C. Ray (Global Change Biology, 2021)
Global commitments to protected area expansion should prioritize opportunities to protect climate refugia and ecosystems which store high levels of irrecoverable carbon, as key components of an effective response to biodiversity loss and climate change. The United States and Canada are responsible for one‐sixth of global greenhouse gas emissions but hold extensive natural ecosystems that store globally significant above‐ and below‐ground carbon. Canada has initiated a process of protected area network expansion in concert with efforts at reconciliation with Indigenous Peoples, and acknowledged nature‐based solutions as a key aspect of climate change mitigation. The US, although not a party to global biodiversity conventions, has recently committed to protecting 30% of its extent by 2030 and achieving the UNFCCC Paris Agreement's mitigation targets. The opportunities afforded by these dual biodiversity conservation and climate commitments require coordinated national and regional policies to ensure that new protected areas maximize biodiversity‐focused adaptation and nature‐based mitigation opportunities. We address how global commitments can best inform national policy initiatives which build on existing agency mandates for regional planning and species conservation. Previous analyses of global conservation priorities under climate change have been tenuously linked to policy contexts of individual nations and have lacked information on refugia due to limitations of globally available datasets. Comparison and synthesis of predictions from a range of recently developed refugia metrics allow such data to inform planning despite substantial uncertainty arising from contrasting model assumptions and inputs. A case study for endangered species planning for old‐forest‐associated species in the US Pacific Northwest demonstrates how regional planning can be nested hierarchically within national biodiversity‐focused adaptation and nature‐based mitigation strategies which integrate refugia, connectivity, and ecosystem carbon metrics to holistically evaluate the role of different land designations and where carbon mitigation and protection of biodiversity's resilience to climate change can be aligned.

Persistence and resistance: survival mechanisms of Candidatus Dormibacterota from nutrient‐poor Antarctic soils - Kate Montgomery; Timothy J. Williams; Merryn Brettle; Jonathan F. Berengut; Angelique E. Ray; Eden Zhang; Julian Zaugg; Philip Hugenholtz; Belinda C. Ferrari (Environmental Microbiology, 2021)
Summary Candidatus Dormibacterota is an uncultured bacterial phylum found predominantly in soil that is present in high abundances within cold desert soils. Here, we interrogate nine metagenome‐assembled genomes ( MAGs ), including six new MAGs derived from soil metagenomes obtained from two eastern Antarctic sites. Phylogenomic and taxonomic analyses revealed these MAGs represent four genera and five species, representing two order‐level clades within Ca . Dormibacterota. Metabolic reconstructions of these MAGs revealed the potential for aerobic metabolism, and versatile adaptations enabling persistence in the ‘extreme’ Antarctic environment. Primary amongst these adaptations were abilities to scavenge atmospheric H 2 and CO as energy sources, as well as using the energy derived from H 2 oxidation to fix atmospheric CO 2 via the Calvin–Bassham–Benson cycle, using a RuBisCO type IE . We propose that these allow Ca . Dormibacterota to persist using H 2 oxidation and grow using atmospheric chemosynthesis in terrestrial Antarctica. Fluorescence in situ hybridization revealed Ca . Dormibacterota to be coccoid cells, 0.3–1.4 μm in diameter, with some cells exhibiting the potential for a symbiotic or syntrophic lifestyle.

The Path to an Ecosystem Approach for Forage Fish Management: A Case Study of Atlantic Menhaden - Kristen A. Anstead; Katie Drew; David Chagaris; Amy M. Schueller; Jason E. McNamee; Andre Buchheister; Geneviève Nesslage; Jim H. Uphoff Jr.; Michael J. Wilberg; Alexei Sharov; Micah J. Dean; Jeffrey Brust; et al. (Frontiers in Marine Science, 2021)
Atlantic menhaden ( Brevoortia tyrannus ) support the largest fishery by volume on the United States East Coast, while also playing an important role as a forage species. Managers’ and stakeholders’ increasing concerns about the impact of Atlantic menhaden harvest on ecosystem processes led to an evolution in the assessment and management of this species from a purely single-species approach to an ecosystem approach. The first coastwide stock assessment of Atlantic menhaden for management used a single-species virtual population analysis (VPA). Subsequent assessments used a forward projecting statistical catch-at-age framework that incorporated estimates of predation mortality from a multispecies VPA while analytical efforts continued toward the development of ecosystem models and explicit ecological reference points (ERPs) for Atlantic menhaden. As an interim step while ecosystem models were being developed, a series of ad hoc measures to preserve Atlantic menhaden biomass for predators were used by managers. In August 2020, the Atlantic States Marine Fisheries Commission formally adopted an ecological modeling framework as a tool to set reference points and harvest limits for the Atlantic menhaden that considers their role as a forage fish. This is the first example of a quantitative ecosystem approach to setting reference points on the United States Atlantic Coast and it represents a significant advance for forage fish management. This case study reviews the history of Atlantic menhaden stock assessments and management, outlines the progress on the current implementation of ERPs for this species, and highlights future research and management needs to improve and expand ecosystem-based fisheries management.

Impact of an SGLT2-loss of function mutation on renal architecture, histology, and glucose homeostasis - Corey B. Hughes; George M. Mussman; Phil Ray; Robert C. Bunn; Virgilius Cornea; Kathryn M. Thrailkill; John L. Fowlkes; Iuliana Popescu (Cell and Tissue Research, 2021)

Serendipita bescii promotes winter wheat growth and modulates the host root transcriptome under phosphorus and nitrogen starvation - Prasun Ray; Yingqing Guo; Myoung‐Hwan Chi; Nick Krom; Malay C. Saha; Kelly D. Craven (Environmental Microbiology, 2021)
Summary Serendipita vermifera ssp. bescii , hereafter referred to as S. bescii , is a root‐associated fungus that promotes plant growth in both its native switchgrass host and a variety of monocots and dicots. Winter wheat ( Triticum aestivum L.), a dual‐purpose crop, used for both forage and grain production, significantly contributes to the agricultural economies of the Southern Great Plains, USA. In this study, we investigated the influence of S. bescii on growth and transcriptome regulation of nitrogen (N) and phosphorus (P) metabolism in winter wheat. Serendipita bescii significantly improved lateral root growth and forage biomass under a limited N or P regime. Further, S. bescii activated sets of host genes regulating N and P starvation responses. These genes include, root‐specific auxin transport, strigolactone and gibberellin biosynthesis, degradation of phospholipids and biosynthesis of glycerolipid, downregulation of ammonium transport and nitrate assimilation, restriction of protein degradation by autophagy and subsequent N remobilization. All these genes are hypothesized to regulate acquisition, assimilation and remobilization of N and P. Based on transcriptional level gene regulation and physiological responses to N or P limitation, we suggest S. bescii plays a critical role in modulating stress imposed by limitation of these two critical nutrients in winter wheat.

Windowing petrogenesis of continental flood basalts through mineralogical investigations: a case study from the Eastern Deccan Volcanic Province - Payel Dey; Jyotisankar Ray; Janisar M. Sheikh; Suresh C. Patel; Christian Koeberl (International Journal of Earth Sciences, 2021)

Correction to: Efficient antileishmanial activity of amphotericin B and piperine entrapped in enteric coated guar gum nanoparticles - Lipika Ray; R. Karthik; Vikas Srivastava; Sheelendra Pratap Singh; A. B. Pant; Neena Goyal; Kailash C. Gupta (Drug Delivery and Translational Research, 2021)

Efficient antileishmanial activity of amphotericin B and piperine entrapped in enteric coated guar gum nanoparticles - Lipika Ray; R. Karthik; Vikas Srivastava; Sheelendra Pratap Singh; A. B. Pant; Neena Goyal; Kailash C. Gupta (Drug Delivery and Translational Research, 2021)

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Not withering on the evolutionary vine: systematic revision of the Brown Vine Snake (Reptilia: Squamata: Oxybelis) from its northern distribution - Robert C. Jadin; Christopher Blair; Sarah A. Orlofske; Michael J. Jowers; Gilson A. Rivas; Laurie J. Vitt; Julie M. Ray; Eric N. Smith; John C. Murphy (Organisms Diversity & Evolution, 2020)

Mapping quantitative trait loci (QTL) for plant nitrogen isotope ratio (δ15N) in soybean - Sumandeep K. Bazzer; Jeffery D. Ray; James R. Smith; Felix B. Fritschi; Larry C. Purcell (Euphytica, 2020)

A Path to a Sustainable Trawl Fishery in Southeast Asia - Petri Suuronen; C. Roland Pitcher; Robert A. McConnaughey; Michel J. Kaiser; Jan G. Hiddink; Ray Hilborn (Reviews in Fisheries Science & Aquaculture, 2020)

Cell-Permeable Calpain Inhibitor SJA6017 Provides Functional Protection to Spinal Motoneurons Exposed to MPP+ - Supriti Samantaray; Varduhi H. Knaryan; Angelo M. Del Re; John J. Woodward; Donald C. Shields; Mitsuyoshi Azuma; Jun Inoue; Swapan K. Ray; Naren L. Banik (Neurotoxicity Research, 2020)

Cancer mortality risk, fine particulate air pollution, and smoking in a large, representative cohort of US adults - Nathan C. Coleman; Richard T. Burnett; Joshua D. Higbee; Jacob S. Lefler; Ray M. Merrill; Majid Ezzati; Julian D. Marshall; Sun-Young Kim; Matthew Bechle; Allen L. Robinson; C. Arden Pope (Cancer Causes & Control, 2020)

Identification of quantitative trait loci for carbon isotope ratio (δ13C) in a recombinant inbred population of soybean - Sumandeep K. Bazzer; Avjinder S. Kaler; Jeffery D. Ray; James R. Smith; Felix B. Fritschi; Larry C. Purcell (Theoretical and Applied Genetics, 2020)

Modeling the impact of rainfall variations and management interventions on the groundwater regime of a hard-rock terrain in central India - Ranjan K. Ray; Tajdarul H. Syed; Dipankar Saha; Bhabesh C. Sarkar (Hydrogeology Journal, 2020)

Choosing best practices for managing impacts of trawl fishing on seabed habitats and biota - Robert A. McConnaughey; Jan G. Hiddink; Simon Jennings; C. Roland Pitcher; Michel J. Kaiser; Petri Suuronen; Marija Sciberras; Adriaan D. Rijnsdorp; Jeremy S. Collie; Tessa Mazor; Ricardo O Amoroso; Ana M. Parma; et al. (Fish and Fisheries, 2020)
Bottom trawling accounts for almost one quarter of global fish landings but may also have significant and unwanted impacts on seabed habitats and biota. Management measures and voluntary industry actions can reduce these impacts, helping to meet sustainability objectives for fisheries, conservation and environmental management. These include changes in gear design and operation of trawls, spatial controls, impact quotas and effort controls. We review nine different measures and actions and use published studies and a simple conceptual model to evaluate and compare their performance. The risks and benefits of these management measures depend on the extent to which the fishery is already achieving management objectives for target stocks and the characteristics of the management system that is already in place. We offer guidance on identifying best practices for trawl‐fisheries management and show that best practices and their likelihood of reducing trawling impacts depend on local, national and regional management objectives and priorities, societal values and resources for implementation. There is no universal best practice, and multiple management measures and industry actions are required to meet sustainability objectives and improve trade‐offs between food production and environmental protection.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Diversity of hepatitis C virus infection among HIV-infected people who inject drugs in India - S. S. Solomon; D. Boon; S. Saravanan; A. K. Srikrishnan; C. K. Vasudevan; P. Balakrishnan; D. Persaud; S. C. Ray; S. Mehta; S. H. Mehta (VirusDisease, 2019)

Grading Herbaceous Biomass for Biorefineries: a Case Study Based on Chemical Composition and Biochemical Conversion - Amber Hoover; Rachel Emerson; C. Luke Williams; M. M. Ramirez-Corredores; Allison Ray; Kastli Schaller; Sergio Hernandez; Chenlin Li; Michelle Walton (BioEnergy Research, 2019)

Revisiting Moisture Transport During the Indian Summer Monsoon Using the Moisture River Concept - Chetana Patil; Thara Prabhakaran; K. C. Sinha Ray; Anandakumar Karipot (Pure and Applied Geophysics, 2019)

Unrecognized and imperilled diversity in an endemic barb (Smiliogastrini, Enteromius ) from the Fouta Djallon highlands - Ray C. Schmidt; Megan N. Dillon; Natalie M. Kuhn; Henry L. Bart; Frank Pezold (Zoologica Scripta, 2019)
The Upper Guinean Forests of Guinea, Sierra Leone and Liberia contain high levels of freshwater biodiversity. The Guinean Range and associated Fouta Djallon highlands separate two biogeographical provinces in the region and served as a refugium during past climatic fluctuations. While many species of freshwater fishes are restricted to one biogeographical province or the other, some are reported to occur on both sides of the divide. Here, we examine the molecular and morphological diversity of an endemic small African barb, Enteromius foutensis , reported to occur in both provinces. This integrative analysis revealed unrecognized diversity and suggests recent, or ongoing, events that facilitated geodispersal and subsequent divergence in the region. The molecular analysis revealed three divergent and well‐supported populations within E. foutensis . Accounting for allometric shape variation allowed us to observe diagnostic morphological differences among the populations. Enteromius foutensis sensu stricto is restricted to the Little Scarcies drainage in Guinea and northern Sierra Leone. Our study revealed two candidate species distinct from E. foutensis . One is likely a narrow endemic restricted to a small area in the Konkouré River basin; the other candidate species inhabits the upper Senegal and Gambie River drainages. How these patterns of diversity compare with other freshwater species from the Fouta Djallon highlands and the conservation status of these candidate species are also discussed.

Early life social and ecological determinants of global DNA methylation in wild spotted hyenas - Zachary M. Laubach; Christopher D. Faulk; Dana C. Dolinoy; Luke Montrose; Tamara R. Jones; Donna Ray; Malit O. Pioon; Kay E. Holekamp (Molecular Ecology, 2019)
Environmental factors early in life can have lasting influence on the development and phenotypes of animals, but the underlying molecular modifications remain poorly understood. We examined cross‐sectional associations among early life socioecological factors and global DNA methylation in 293 wild spotted hyenas ( Crocuta crocuta ) in the Masai Mara National Reserve, Kenya, grouped according to three age classes (cub, subadult and adult). Explanatory variables of interest included annual maternal rank based on outcomes of dyadic agonistic interactions, litter size, wild ungulate prey density and anthropogenic disturbance in the year each hyena was born based on counts of illegal livestock in the Reserve. The dependent variable of interest was global DNA methylation, assessed via the LUminometric Methylation Assay, which provides a percentage methylation value calculated at CCGG sites across the genome. Among cubs, we observed approximately 2.75% higher CCGG methylation in offspring born to high‐ than low‐ranking mothers. Among cubs and subadults, higher anthropogenic disturbance corresponded with greater %CCGG methylation. In both cubs and adults, we found an inverse association between prey density measured before a hyena was 3 months old and %CCGG methylation. Our results suggest that maternal rank, anthropogenic disturbance and prey availability early in life are associated with later life global DNA methylation. Future studies are required to understand the extent to which these DNA methylation patterns relate to adult phenotypes and fitness outcomes.

Radiological Estimation of Intracranial Blood Volume and Occurrence of Hydrocephalus Determines Stress-Induced Hyperglycemia After Aneurysmal Subarachnoid Hemorrhage - Joshua A Santucci; Stephen R Ross; John C Greenert; Faranak Aghaei; Lance Ford; Kimberly M Hollabaugh; Benjamin O Cornwell; Dee H Wu; Bin Zheng; Bradley N Bohnstedt; Bappaditya Ray (Translational Stroke Research, 2019)

Over-expression of Hsp83 in grossly depleted hsrω lncRNA background causes synthetic lethality and l(2)gl phenocopy in Drosophila - Mukulika Ray; Sundaram Acharya; Sakshi Shambhavi; Subhash C Lakhotia (Journal of Biosciences, 2019)

Targeting autophagy for combating chemoresistance and radioresistance in glioblastoma - Matthew A. Taylor; Bhaskar C. Das; Swapan K. Ray (Apoptosis, 2018)

Biogenic hydrogen sulphide emissions and non-sea sulfate aerosols over the Indian Sundarban mangrove forest - D. Ganguly; R. Ray; N. Majumdar; C. Chowdhury; T. K. Jana (Journal of Atmospheric Chemistry, 2018)

Association mapping identifies loci for canopy temperature under drought in diverse soybean genotypes - Avjinder S. Kaler; Jeffery D. Ray; William T. Schapaugh; Antonio R. Asebedo; C. Andy King; E. E. Gbur; Larry C. Purcell (Euphytica, 2018)

Modelling broad‐scale wolverine occupancy in a remote boreal region using multi‐year aerial survey data - Justina C. Ray; Lucy G. Poley; Audrey J. Magoun; Cheryl‐Lesley B. Chetkiewicz; F. Meg Southee; F. Neil Dawson; Chris Chenier (Journal of Biogeography, 2018)
Aim We used data from aerial surveys of wolverine tracks collected in seven winters over a 10‐year period (2003–2012) within a 574,287 km 2 study area to evaluate the broad‐scale pattern of wolverine occurrence across a remote northern boreal forest region, identifying areas of high and low occupancy. Location Northern Ontario, Canada. Taxon Wolverine ( Gulo gulo Linnaeus, 1758). Methods We collected wolverine tracks and observations in 100‐km 2 hexagonal survey units, making a total of 6,664 visits to 3,039 units, visiting each 1–9 times. We used hierarchical Bayesian occupancy modelling to model wolverine occurrence, and included covariates with the potential to affect detection and/or occupancy probability of wolverines. Results we detected wolverines on 946 visits, 14.2% of total visits. Probability of detecting a wolverine varied among years and between the two ecozones in the study area. Wolverine occupancy was negatively related to two important covariates, the geographical coordinate Easting and thawing degree‐days. A site occupancy probability map indicated that wolverine occupancy probabilities were highest, and standard error lowest, in the western and northern portions of the study area. Main conclusions The occupancy framework enabled us to use observation data from tracks of this elusive, wide‐ranging carnivore over a vast, remote area while explicitly considering detectability and spatial autocorrelation, yielding a map of probable wolverine distribution in northern Ontario that would not be possible using other methods of detection across a large region. With resource development pressures increasing in this globally significant region in the face of a changing climate, it is important to monitor changes in distribution of species like wolverines that have low population growth rates, large spatial requirements and sensitivity to human disturbance. This study demonstrates a relatively cost‐effective and non‐invasive alternative to monitoring based on wolverine harvest records, which have not been available since 2009 in Ontario due to changes in the provincial regulatory regime for this threatened species.

Response of benthic fauna to experimental bottom fishing: A global meta‐analysis - Marija Sciberras; Jan Geert Hiddink; Simon Jennings; Claire L Szostek; Kathryn M Hughes; Brian Kneafsey; Leo J Clarke; Nick Ellis; Adriaan D Rijnsdorp; Robert A McConnaughey; Ray Hilborn; Jeremy S Collie; et al. (Fish and Fisheries, 2018)
Bottom‐contact fishing gears are globally the most widespread anthropogenic sources of direct disturbance to the seabed and associated biota. Managing these fishing disturbances requires quantification of gear impacts on biota and the rate of recovery following disturbance. We undertook a systematic review and meta‐analysis of 122 experiments on the effects‐of‐bottom fishing to quantify the removal of benthos in the path of the fishing gear and to estimate rates of recovery following disturbance. A gear pass reduced benthic invertebrate abundance by 26% and species richness by 19%. The effect was strongly gear‐specific, with gears that penetrate deeper into the sediment having a significantly larger impact than those that penetrate less. Sediment composition (% mud and presence of biogenic habitat) and the history of fishing disturbance prior to an experimental fishing event were also important predictors of depletion, with communities in areas that were not previously fished, predominantly muddy or biogenic habitats being more strongly affected by fishing. Sessile and low mobility biota with longer life‐spans such as sponges, soft corals and bivalves took much longer to recover after fishing (>3 year) than mobile biota with shorter life‐spans such as polychaetes and malacostracans (

Phosphorus Budget of the Sundarban Mangrove Ecosystem: Box Model Approach - R. Ray; N. Majumder; C. Chowdhury; S. Das; T. K. Jana (Estuaries and Coasts, 2018)

Consideration of carbon dioxide release during shell production in LCA of bivalves - Nicholas E. Ray; Teri O’Meara; Timothy Wiliamson; Jose-Luis Izursa; Patrick C. Kangas (The International Journal of Life Cycle Assessment, 2018)

Differential expression of hormone related genes between extreme segregants of a Saccharum interspecific F2 population - Fan Zhu; Ching Man Wai; Jisen Zhang; Tyler C. Jones; Chifumi Nagai; Ray Ming (Euphytica, 2018)

Management effectiveness of large pelagic fisheries in the high seas - Maite Pons; Michael C Melnychuk; Ray Hilborn (Fish and Fisheries, 2018)
Large pelagic fishes are assessed and managed by tuna Regional Fisheries Management Organizations ( tRFMO s). These organizations have been criticized for not meeting conservation objectives, which may relate to aspects of governance and management. No previous studies have systematically evaluated why management performance differs among tRFMO s and among stocks within each tRFMO . In this study, we collected data on the nature of research, management, enforcement and socioeconomics of management systems in the five principal tRFMO s of the world's oceans. We quantified influences of economic and fishery‐related factors on these management characteristics and examined how these factors vary among tRFMO s. We found that tRFMO s with a greater number of member countries, a greater economic dependency on tuna resources, a lower mean per capita gross domestic product, a greater number of fishing vessels and smaller vessels were associated with less intensive research, management and enforcement in these tuna fisheries. We also quantified the influence of specific management attributes and of biological, economic and fishery‐related factors on the trends and current status of large pelagic fish stocks in these regions. The most important factors correlated with trends and current stock status were external to the management systems, and included stock size, age at maturity, ex‐vessel price and economic dependency of countries on tuna fisheries. To improve the overall status of large pelagic fish stocks in the global high seas, more intensive data collection, research and management are needed in certain areas, especially in the Indian Ocean, and for certain stocks, especially non‐target species.

A novel Chromatiales bacterium is a potential sulfide oxidizer in multiple orders of marine sponges - Adi Lavy; Ray Keren; Ke Yu; Brian C. Thomas; Lisa Alvarez‐Cohen; Jillian F. Banfield; Micha Ilan (Environmental Microbiology, 2018)
Summary Sponges are benthic filter feeders that play pivotal roles in coupling benthic‐pelagic processes in the oceans that involve transformation of dissolved and particulate organic carbon and nitrogen into biomass. While the contribution of sponge holobionts to the nitrogen cycle has been recognized in past years, their importance in the sulfur cycle, both oceanic and physiological, has only recently gained attention. Sponges in general, and Theonella swinhoei in particular, harbour a multitude of associated microorganisms that could affect sulfur cycling within the holobiont. We reconstructed the genome of a Chromatiales (class Gammaproteobacteria) bacterium from a metagenomic sequence dataset of a T. swinhoei ‐associated microbial community. This relatively abundant bacterium has the metabolic capability to oxidize sulfide yet displays reduced metabolic potential suggestive of its lifestyle as an obligatory symbiont. This bacterium was detected in multiple sponge orders, according to similarities in key genes such as 16S rRNA and polyketide synthase genes. Due to its sulfide oxidation metabolism and occurrence in many members of the Porifera phylum, we suggest naming the newly described taxon Candidatus Porisulfidus .

Erratum: Assessment of village-wise groundwater draft for irrigation: a field-based study in hard-rock aquifers of central India - R. K. Ray; T. H. Syed; Dipankar Saha; B. C. Sarkar; A. K. Patre (Hydrogeology Journal, 2017)

Assessment of village-wise groundwater draft for irrigation: a field-based study in hard-rock aquifers of central India - R. K. Ray; T. H. Syed; Dipankar Saha; B. C. Sarkar; A. K. Patre (Hydrogeology Journal, 2017)

Genome-wide association mapping of canopy wilting in diverse soybean genotypes - Avjinder S. Kaler; Jeffery D. Ray; William T. Schapaugh; C. Andy King; Larry C. Purcell (Theoretical and Applied Genetics, 2017)

Migratory stopover timing is predicted by breeding latitude, not habitat quality, in a long-distance migratory songbird - A. Van Loon; J. D. Ray; A. Savage; J. Mejeur; L. Moscar; M. Pearson; M. Pearman; G. T. Hvenegaard; N. Mickle; K. Applegate; K. C. Fraser (Journal of Ornithology, 2017)

Decadal declines in avian herbivore reproduction: density‐dependent nutrition and phenological mismatch in the Arctic - Megan V. Ross; Ray T. Alisauskas; David C. Douglas; Dana K. Kellett (Ecology, 2017)
A full understanding of population dynamics depends not only on estimation of mechanistic contributions of recruitment and survival, but also knowledge about the ecological processes that drive each of these vital rates. The process of recruitment in particular may be protracted over several years, and can depend on numerous ecological complexities until sexually mature adulthood is attained. We addressed long‐term declines (23 breeding seasons, 1992–2014) in the per capita production of young by both Ross's Geese ( Chen rossii ) and Lesser Snow Geese ( Chen caerulescens caerulescens ) nesting at Karrak Lake in Canada's central Arctic. During this period, there was a contemporaneous increase from 0.4 to 1.1 million adults nesting at this colony. We evaluated whether (1) density‐dependent nutritional deficiencies of pre‐breeding females or (2) phenological mismatch between peak gosling hatch and peak forage quality, inferred from NDVI on the brood‐rearing areas, may have been behind decadal declines in the per capita production of goslings. We found that, in years when pre‐breeding females arrived to the nesting grounds with diminished nutrient reserves, the proportional composition of young during brood‐rearing was reduced for both species. Furthermore, increased mismatch between peak gosling hatch and peak forage quality contributed additively to further declines in gosling production, in addition to declines caused by delayed nesting with associated subsequent negative effects on clutch size and nest success. The degree of mismatch increased over the course of our study because of advanced vegetation phenology without a corresponding advance in Goose nesting phenology. Vegetation phenology was significantly earlier in years with warm surface air temperatures measured in spring (i.e., 25 May–30 June). We suggest that both increased phenological mismatch and reduced nutritional condition of arriving females were behind declines in population‐level recruitment, leading to the recent attenuation in population growth of Snow Geese.

Potential impacts of bioprocessing of sweet potato: Review - Aly Farag El Sheikha; Ramesh C. Ray (Critical Reviews in Food Science and Nutrition, 2017)

A LC-MS/MS Method for Quantifying Adenosine, Guanosine and Inosine Nucleotides in Human Cells - Leah C. Jimmerson; Lane R. Bushman; Michelle L. Ray; Peter L. Anderson; Jennifer J. Kiser (Pharmaceutical Research, 2017)

Effects of biological, economic and management factors on tuna and billfish stock status - Maite Pons; Trevor A Branch; Michael C Melnychuk; Olaf P Jensen; Jon Brodziak; Jean M Fromentin; Shelton J Harley; Alan C Haynie; Laurie T Kell; Mark N Maunder; Ana M Parma; Victor R Restrepo; et al. (Fish and Fisheries, 2017)
Commercial tunas and billfishes (swordfish, marlins and sailfish) provide considerable catches and income in both developed and developing countries. These stocks vary in status from lightly exploited to rebuilding to severely depleted. Previous studies suggested that this variability could result from differences in life‐history characteristics and economic incentives, but differences in exploitation histories and management measures also have a strong effect on current stock status. Although the status (biomass and fishing mortality rate) of major tuna and billfish stocks is well documented, the effect of these diverse factors on current stock status and the effect of management measures in rebuilding stocks have not been analysed at the global level. Here, we show that, particularly for tunas, stocks were more depleted if they had high commercial value, were long‐lived species, had small pre‐fishing biomass and were subject to intense fishing pressure for a long time. In addition, implementing and enforcing total allowable catches ( TAC s) had the strongest positive influence on rebuilding overfished tuna and billfish stocks. Other control rules such as minimum size regulations or seasonal closures were also important in reducing fishing pressure, but stocks under TAC implementations showed the fastest increase of biomass. Lessons learned from this study can be applied in managing large industrial fisheries around the world. In particular, tuna regional fisheries management organizations should consider the relative effectiveness of management measures observed in this study for rebuilding depleted large pelagic stocks.

Characterization of Vermicomposts Prepared from Agricultural Solid Wastes in North Eastern Hill Region of Nagaland, India - Dibyendu Chatterjee; Rukuosietuo Kuotsu; Z. James Kikon; Dibyendu Sarkar; Merasenla Ao; Sanjay Kumar Ray; Tanumoy Bera; Bidyut C. Deka (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

The future of nemertean taxonomy (phylum Nemertea) — a proposal - Per Sundberg; Sónia C. S. Andrade; Thomas Bartolomaeus; Patrick Beckers; Jörn von Döhren; Daria Krämer; Ray Gibson; Gonzalo Giribet; Alfonso Herrera‐Bachiller; Juan Junoy; Hiroshi Kajihara; Sebastian Kvist; et al. (Zoologica Scripta, 2016)

Metabarcoding and metabolome analyses of copepod grazing reveal feeding preference and linkage to metabolite classes in dynamic microbial plankton communities - Jessica L. Ray; Julia Althammer; Katrine S. Skaar; Paolo Simonelli; Aud Larsen; Diane Stoecker; Andrey Sazhin; Umer Z. Ijaz; Christopher Quince; Jens C. Nejstgaard; Marc Frischer; Georg Pohnert; et al. (Molecular Ecology, 2016)
In order to characterize copepod feeding in relation to microbial plankton community dynamics, we combined metabarcoding and metabolome analyses during a 22‐day seawater mesocosm experiment. Nutrient amendment of mesocosms promoted the development of haptophyte ( Phaeocystis pouchetii )‐ and diatom ( Skeletonema marinoi )‐dominated plankton communities in mesocosms, in which Calanus sp. copepods were incubated for 24 h in flow‐through chambers to allow access to prey particles ( P. pouchetii , were passively consumed or even negatively selected according to our indicator. Our analysis of the relationship between Calanus grazing ratios and intracellular metabolite profiles indicates the importance of carbohydrates and lipids in plankton succession and copepod–prey interactions. This molecular characterization of Calanus sp. grazing therefore provides new evidence for selective feeding in mixed plankton assemblages and corroborates previous findings that copepod grazing may be coupled to the developmental and metabolic stage of the entire prey community rather than to individual prey abundances.

Temperature dependent growth rate of phytoplankton and salinity induced grazing rate of zooplankton as determinants of realistic multi-delayed food chain model - Ujjwal Roy; N. C. Majee; Santanu Ray (Modeling Earth Systems and Environment, 2016)

Ascospore release and discharge distances of Fusarium graminearum under controlled temperature and relative humidity - Ray F. David; Linsey C. Marr; David G. Schmale (European Journal of Plant Pathology, 2016)

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

Photosynthesis rate, salinity induced grazing rate and gestation delay as determinants of the dynamics of a realistic food chain model: a stochastic approach - Ujjwal Roy; N. C. Majee; Santanu Ray (Modeling Earth Systems and Environment, 2016)

Identification of meteorological predictors of Fusarium graminearum ascospore release using correlation and causality analyses - Ray F. David; Amir E. BozorgMagham; David G. Schmale; Shane D. Ross; Linsey C. Marr (European Journal of Plant Pathology, 2016)

Standardization of a method for studying susceptibility of Indian coals to self-heating - Haider Banka; Santosh Kr. Ray; D. C. Panigrahi (Arabian Journal of Geosciences, 2016)

Real‐time spatial management approaches to reduce bycatch and discards: experiences from Europe and the United States - Alyson S Little; Coby L Needle; Ray Hilborn; Daniel S Holland; C Tara Marshall (Fish and Fisheries, 2015)
Spatial management measures are currently being used to manage bycatch and discards, given the spatial heterogeneity of fish distributions. However, permanent fishing closures are often poorly implemented, unresponsive to stock dynamics and do not achieve their management objectives. Recently, real‐time spatial management tools for managing bycatch and discards implemented under either a comanagement or self‐governance approach have been introduced in Europe and the US . Real‐time catch and discard information is shared among fishers to incentivise and encourage vessels to leave areas of high bycatch. Here, the similarities and differences, in governance, implementation and management of ten real‐time spatial management systems from across Europe and the US are reviewed. A framework is developed to characterize the attributes associated with voluntary, private and regulatory real‐time spatial management tools. Challenges and management practices in the different case studies are reviewed providing insights for designing these spatial management tools. The results illustrate that real‐time spatial management approaches can create incentives for fishers to develop, use and share information and technology to avoid undesired catch. Compared with Europe, the US has developed spatial management tools with more truly real‐time mechanisms and with greater involvement of the fishing industry in designing and operating the tools.

Confirmation of delayed canopy wilting QTLs from multiple soybean mapping populations - Sadal Hwang; C. Andy King; Jeffery D. Ray; Perry B. Cregan; Pengyin Chen; Thomas E. Carter; Zenglu Li; Hussein Abdel-Haleem; Kevin W. Matson; William Schapaugh; Larry C. Purcell (Theoretical and Applied Genetics, 2015)

Genistein ameliorates cardiac inflammation and oxidative stress in streptozotocin-induced diabetic cardiomyopathy in rats - Suresh K. Gupta; Shirish Dongare; Rajani Mathur; Ipseeta Ray Mohanty; Sushma Srivastava; Sandeep Mathur; Tapas C. Nag (Molecular and Cellular Biochemistry, 2015)

A New Vision for the Eye: Unmet Ocular Drug Delivery Needs - Hongwen M. Rivers; Siladitya Ray Chaudhuri; Jaymin C. Shah; Sachin Mittal (Pharmaceutical Research, 2015)

Challenges and Opportunities for Customizing Polyhydroxyalkanoates - Mamtesh Singh; Prasun Kumar; Subhasree Ray; Vipin C. Kalia (Indian Journal of Microbiology, 2015)

The commonly used eye-specific sev-GAL4 and GMR-GAL4 drivers in Drosophila melanogaster are expressed in tissues other than eyes also - MUKULIKA RAY; SUBHASH C. LAKHOTIA (Journal of Genetics, 2015)

Science–policy processes for transboundary water governance - Derek Armitage; Rob C. de Loë; Michelle Morris; Tom W. D. Edwards; Andrea K. Gerlak; Roland I. Hall; Dave Huitema; Ray Ison; David Livingstone; Glen MacDonald; Naho Mirumachi; Ryan Plummer; et al. (Ambio, 2015)

(2S,4E)-2-Hydroxy-4-octen-3-one, a Male-Produced Attractant Pheromone of the Cerambycid Beetle Tylonotus bimaculatus - Yunfan Zou; Jocelyn G. Millar; J. Scott Blackwood; Ryan Van Duzor; Lawrence M. Hanks; Judith A. Mongold-Diers; Joseph C. H. Wong; Ann M. Ray (Journal of Chemical Ecology, 2015)

Habitat Characteristics and Their Effects on the Density of Groups of Western Hoolock Gibbon (Hoolock hoolock) in Namdapha National Park, Arunachal Pradesh, India - Parimal Chandra Ray; Awadhesh Kumar; Ashalata Devi; Murali C. Krishna; M. L. Khan; W. Y. Brockelman (International Journal of Primatology, 2015)

Peralkaline felsic magmatism at the Nemrut volcano, Turkey: impact of volcanism on the evolution of Lake Van (Anatolia) IV - Ray Macdonald; Mari Sumita; Hans-Ulrich Schmincke; Bogusław Bagiński; John C. White; Sławomir S. Ilnicki (Contributions to Mineralogy and Petrology, 2015)

Geochemistry of PGE in mafic rocks of east Khasi Hills, Shillong Plateau, NE India - Sampa Hazra; Jyotisankar Ray; C Manikyamba; Abhishek Saha; S S Sawant (Journal of Earth System Science, 2015)

Erratum to: Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

Estimation of flood damage functions for river basin planning: a case study in Bangladesh - Y. C. Ethan Yang; Patrick A. Ray; Casey M. Brown; Abedalrazq F. Khalil; Winston H. Yu (Natural Hazards, 2015)

Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

Methane and nitrous oxide emissions from rice and maize production in diversified rice cropping systems - Sebastian Weller; David Kraus; Kevin Ray P. Ayag; Reiner Wassmann; M. C. R. Alberto; Klaus Butterbach-Bahl; Ralf Kiese (Nutrient Cycling in Agroecosystems, 2015)

Assessment of organochlorine pesticide residues in Indian flue-cured tobacco with gas chromatography-single quadrupole mass spectrometer - Rakesh Kumar Ghosh; Zareen S. Khan; C. V. N. Rao; Kaushik Banerjee; D. Damodar Reddy; T. G. K. Murthy; Nalli Johnson; Deb Prasad Ray (Environmental Monitoring and Assessment, 2014)

Quantitative Study of As (V) and As (III) Interaction with Mangrove DNA by Molecular Fluorescence Spectroscopy - N. Majumder; C. Chowdhury; R. Ray; T. K. Jana (Bulletin of Environmental Contamination and Toxicology, 2014)

The adaptive capacity of fishery management systems for confronting climate change impacts on marine populations - Michael C. Melnychuk; Jeannette A. Banobi; Ray Hilborn (Reviews in Fish Biology and Fisheries, 2014)

Trends in seasonal temperatures over the Indian region - Nilesh K Wagholikar; K C Sinha Ray; P N Sen; P Pradeep Kumar (Journal of Earth System Science, 2014)

Secondary cell wall composition and candidate gene expression in developing willow (Salix purpurea) stems - Yongfang Wan; Cristina Gritsch; Theodora Tryfona; Mike J. Ray; Ambrose Andongabo; Keywan Hassani-Pak; Huw D. Jones; Paul Dupree; Angela Karp; Peter R. Shewry; Rowan A. C. Mitchell (Planta, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Genetics and mapping of quantitative traits for nodule number, weight, and size in soybean (Glycine max L.[Merr.]) - Sadal Hwang; Jeffery D. Ray; Perry B. Cregan; C. Andy King; Marilynn K. Davies; Larry C. Purcell (Euphytica, 2014)

Occupancy patterns of large mammals in the Far North of Ontario under imperfect detection and spatial autocorrelation - Lucy G. Poley; Bruce A. Pond; James A. Schaefer; Glen S. Brown; Justina C. Ray; Devin S. Johnson (Journal of Biogeography, 2014)
Aim An understanding of the factors that influence species distributions in heterogeneous landscapes is important when making decisions regarding conservation. Moreover, occupancy probabilities based on detection data can reveal important species–habitat relationships. Accounting for the spatial autocorrelation of detection data increases the statistical validity of occupancy models, but is not often considered. Using novel occupancy modelling that explicitly incorporates detectability and spatial autocorrelation, we assessed the influence of habitat on occupancy patterns of woodland caribou ( Rangifer tarandus caribou ), moose ( Alces alces ) and wolves ( Canis lupus ) across a broad biogeographical extent where fire is the dominant agent of disturbance. Location Northern Ontario, Canada. Methods We aerially surveyed 3851 sampling units, each covering 100 km 2 , for woodland caribou, moose and wolves in February–March in 2009, 2010 and 2011, and visited 1663 units more than once to estimate detectability. We used restricted spatial regression to model occupancy probabilities of each species with respect to habitat factors in two ecozones, accounting for both imperfect detection and lack of independence of sampling units. Results Covariates influencing species detection varied among ecozones and species. Caribou occupancy was positively related to bogs and negatively related to disturbed areas, while moose occupancy showed opposite responses to these covariates. Wolf occupancy was related to high prey occupancy. Explicitly accounting for spatial autocorrelation in detection data reduced the chance of type I error in occupancy estimates compared with non‐spatial models. Main conclusions Habitat relationships and occupancy patterns support the hypothesis that caribou remain spatially segregated from moose to reduce predation risk. The broad scale of analysis indicated changes in species–habitat relationships, suggesting that limiting factors vary across biogeographical gradients. The spatial pattern in caribou occupancy allowed us to identify important areas used by caribou across the region, including the ecotone between fire‐driven boreal forests and peatland complexes. The evidence for significant relationships between caribou and land cover, predators and alternate prey underscores the need for careful planning of development and infrastructure in the area.

Targeting oncogenic ALK and MET: a promising therapeutic strategy for glioblastoma - Gerald C. Wallace; Yaenette N. Dixon-Mah; W. Alex Vandergrift; Swapan K. Ray; Catherine P. Haar; Amber M. Mittendorf; Sunil J. Patel; Naren L. Banik; Pierre Giglio; Arabinda Das (Metabolic Brain Disease, 2013)

Impact of acamprosate on behavior and brain-derived neurotrophic factor: an open-label study in youth with fragile X syndrome - Craig A. Erickson; Logan K. Wink; Balmiki Ray; Maureen C. Early; Elizabeth Stiegelmeyer; Lauren Mathieu-Frasier; Vanessa Patrick; Debomoy K. Lahiri; Christopher J. McDougle (Psychopharmacology, 2013)

Comparative pharmacokinetics of PAMAM-OH dendrimers and HPMA copolymers in ovarian tumor-bearing mice - S. Sadekar; O. Linares; G. J. Noh; D. Hubbard; A. Ray; M. Janát-Amsbury; C. M. Peterson; J. Facelli; H. Ghandehari (Drug Delivery and Translational Research, 2013)

Implication of Organic Matter on Arsenic and Antimony Sequestration in Sediment: Evidence from Sundarban Mangrove Forest, India - S. K. Mandal; R. Ray; C. Chowdhury; N. Majumder; T. K. Jana (Bulletin of Environmental Contamination and Toxicology, 2013)

Spatial occupancy models for large data sets - Devin S. Johnson; Paul B. Conn; Mevin B. Hooten; Justina C. Ray; Bruce A. Pond (Ecology, 2013)
Since its development, occupancy modeling has become a popular and useful tool for ecologists wishing to learn about the dynamics of species occurrence over time and space. Such models require presence–absence data to be collected at spatially indexed survey units. However, only recently have researchers recognized the need to correct for spatially induced overdisperison by explicitly accounting for spatial autocorrelation in occupancy probability. Previous efforts to incorporate such autocorrelation have largely focused on logit‐normal formulations for occupancy, with spatial autocorrelation induced by a random effect within a hierarchical modeling framework. Although useful, computational time generally limits such an approach to relatively small data sets, and there are often problems with algorithm instability, yielding unsatisfactory results. Further, recent research has revealed a hidden form of multicollinearity in such applications, which may lead to parameter bias if not explicitly addressed. Combining several techniques, we present a unifying hierarchical spatial occupancy model specification that is particularly effective over large spatial extents. This approach employs a probit mixture framework for occupancy and can easily accommodate a reduced‐dimensional spatial process to resolve issues with multicollinearity and spatial confounding while improving algorithm convergence. Using open‐source software, we demonstrate this new model specification using a case study involving occupancy of caribou ( Rangifer tarandus ) over a set of 1080 survey units spanning a large contiguous region (108 000 km 2 ) in northern Ontario, Canada. Overall, the combination of a more efficient specification and open‐source software allows for a facile and stable implementation of spatial occupancy models for large data sets.

Using Vegetative Nutrient Stocks to Compare Restored and Reference Wetlands in the Upper Klamath Basin, Oregon - Andrew M. Ray; Andy Hamilton; Chelsea Aquino; James C. Litts (Wetlands, 2012)

Phosphorus Solubilization by Thermotolerant Bacillus subtilis Isolated from Cow Dung Microflora - Manas R. Swain; K. Laxminarayana; Ramesh C. Ray (Agricultural Research, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Effect of Fungicides and Insecticides on Growth and Enzyme Activity of Four Cyanobacteria - Manojit Debnath; Narayan C. Mandal; Samit Ray (Indian Journal of Microbiology, 2012)

Genome size variation in three Saccharum species - Jisen Zhang; Chifumi Nagai; Qingyi Yu; Yong-Bao Pan; Tomas Ayala-Silva; Raymond J. Schnell; Jack C. Comstock; Aru K. Arumuganathan; Ray Ming (Euphytica, 2012)

Pilot study to integrate existing karst flow data for Kentucky, USA into the National Hydrography Dataset of US Geological Survey - Robert J. Blair; E. Deven Carigan; James C. Currens; Phillip W. O’dell; Joseph A. Ray; James E. Seay (Carbonates and Evaporites, 2012)

Particle Size Distribution of Ambient Aerosols in an Industrial Area - B. Padma Rao; A. Srivastava; F. Yasmin; S. Ray; N. Gupta; C. Chauhan; C. V. C. Rao; S. R. Wate (Bulletin of Environmental Contamination and Toxicology, 2012)

Connectivity of prairie dog colonies in an altered landscape: inferences from analysis of microsatellite DNA variation - Loren C. Sackett; Todd B. Cross; Ryan T. Jones; Whitney C. Johnson; Kimberly Ballare; Chris Ray; Sharon K. Collinge; Andrew P. Martin (Conservation Genetics, 2012)

Isolation and characterization of polymorphic microsatellite loci from the invasive plant Lantana camara L. - Avik Ray; R. C. Sumangala; G. Ravikanth; R. Uma Shaanker; Suhel Quader (Conservation Genetics Resources, 2012)

The sex-specific region of sex chromosomes in animals and plants - Andrea R. Gschwend; Laura A. Weingartner; Richard C. Moore; Ray Ming (Chromosome Research, 2012)

Linked gene networks involved in nitrogen and carbon metabolism and levels of water-soluble carbohydrate accumulation in wheat stems - C. Lynne McIntyre; Rosanne E. Casu; Allan Rattey; M. Fernanda Dreccer; Jason W. Kam; Anthony F. van Herwaarden; Ray Shorter; Gang Ping Xue (Functional & Integrative Genomics, 2011)

A Spatial Database of Cropping System and its Characteristics to Aid Climate Change Impact Assessment Studies - Sushma Panigrahy; Shibendu Shankar Ray; K. R. Manjunath; P. S. Pandey; S. K. Sharma; Anil Sood; Manoj Yadav; P. C. Gupta; N. Kundu; Jai Singh Parihar (Journal of the Indian Society of Remote Sensing, 2011)

VEGF-C differentially regulates VEGF-A expression in ocular and cancer cells; promotes angiogenesis via RhoA mediated pathway - Bharat Kumar; Shailaja A. Chile; Kriti B. Ray; G. E. C. Vidyadhar Reddy; Murali K. Addepalli; A. S. Manoj Kumar; Venkata Ramana; Vikram Rajagopal (Angiogenesis, 2011)

Deriving biomedical diagnostics from NMR spectroscopic data - Ian C. P. Smith; Ray L. Somorjai (Biophysical Reviews, 2011)

Carbon Inputs and Water Uptake in Deep Soils of an Eastern Amazon Forest - Eric Davidson; Paul A. Lefebvre; Paulo M. Brando; David M. Ray; Susan E. Trumbore; Luis A. Solorzano; Joice N. Ferreira; Mercedes M. da C. Bustamante; Daniel C. Nepstad (Forest Science, 2011)
Rooting depth affects soil profiles of water uptake and carbon inputs. Here we explore the importance of deep roots in a mature tropical forest of eastern Amazonia, where a throughfall exclusion experiment was conducted to test the resilience of the forest to experimentally induced drought. We hypothesized that soil water depletion occurred below the depth previously measured by sensors in 11-m-deep soil pits and that only a small root biomass is necessary to affect water uptake and the isotopic signature of soil CO2. A noninvasive electrical profiling method demonstrated greater depletion of soil water in the 11-18 m depth increment in the exclusion plot compared with the control plot by the end of the 3rd year of the experiment. A fine root biomass of only 0.1 g/cm3 measured at 3-6 m was sufficient for soil water drawdown and for imparting an isotopic signature of modern soil 14CO2 in both plots. A soil 13CO2 profile indicated drought stress in the exclusion plot. Fine root inputs of organic C to deep soils are small with respect to the carbon dynamics of the forest, but the deep rooting habit clearly affects the ecosystem water balance and profiles of soil CO2.

Effects of crop type on persistence and control efficacy of Beauveria bassiana against the two spotted spider mite - Mutimura C. Gatarayiha; Mark D. Laing; Ray M. Miller (BioControl, 2010)

A regional scale assessment of land use/land cover and climatic changes on water and energy cycle in the upper Midwest United States - Vimal Mishra; Keith A. Cherkauer; Dev Niyogi; Ming Lei; Bryan C. Pijanowski; Deepak K. Ray; Laura C. Bowling; Guoxiang Yang (International Journal of Climatology, 2010)
This study examines the relative impact of regional land‐cover/land‐use patterns and projected future climate change on hydrologic processes. Historic, present and projected future land cover data were used to drive the variable infiltration capacity (VIC) model using observed meteorological forcing data for 1983–2007 over Wisconsin (USA). The current and projected future (year 2030) land cover data were developed using the land transformation model (LTM). The VIC model simulations were driven using downscaled and bias‐corrected projected future climate forcing from three different Intergovernmental Panel for Climate Change (IPCC) AR4 general circulation models (GCMs): HadCM3, PCM and GFDL. Sensitivity results conducted on a single grid cell show that annual average surface runoff and baseflow were increased by 8 and 6 mm, respectively, while evapotranspiration was reduced by 15 mm when a fully forested grid was converted to cropland. Results also indicate that annual average net radiation and sensible heat flux were reduced considerably due to forest‐to‐cropland conversion, and the reduction was more prominent in winter and spring seasons due to effect of snow albedo. Forest‐to‐cropland conversion also resulted in increased latent heat flux in summer (JJA) while this land transformation increased the snow water equivalent in winter (DJF) and spring (MAM). Complete conversion of forest to cropland resulted in a decrease of the radiative surface temperature on an annual basis with more cooling occurring in winter and summer. Impacts of historic deforestation were similar to what was expected based on a single grid sensitivity analysis. Copyright © 2010 Royal Meteorological Society

Major ash eruptions of Barren Island volcano (Andaman Sea) during the past 72 kyr: clues from a sediment core record - Neeraj Awasthi; Jyotiranjan S. Ray; Amzad H. Laskar; Alok Kumar; M. Sudhakar; Rajneesh Bhutani; Hetu C. Sheth; Madhusudan G. Yadava (Bulletin of Volcanology, 2010)

Evaluating the protection of wildlife in parks: the case of African buffalo in Serengeti - K. L. Metzger; A. R. E. Sinclair; Ray Hilborn; J. Grant C. Hopcraft; Simon A. R. Mduma (Biodiversity and Conservation, 2010)

Feasibility Evaluation of Pressurized Irrigation in Canal Commands - Ramesh C. Srivastava; Sheelabhadra Mohanty; Ramlal B. Singandhuppe; Rajiv K. Mohanty; Madhu S. Behera; Lala I. P. Ray; Deepika Sahoo (Water Resources Management, 2010)

The Impact of Future Land Use Scenarios on Runoff Volumes in the Muskegon River Watershed - Deepak K. Ray; Jonah M. Duckles; Bryan C. Pijanowski (Environmental Management, 2010)

Shift in detrital sedimentation in the eastern Bay of Bengal during the late Quaternary - C. Prakash Babu; J. N. Pattan; K. Dutta; N. Basavaiah; G. V. Ravi Prasad; D. K. Ray; P. Govil (Journal of Earth System Science, 2010)

Ethanol fermentation of mahula (Madhuca latifolia) flowers using free and immobilized bacteria Zymomonas mobilis MTCC 92 - Shuvashish Behera; Rama C. Mohanty; Ramesh C. Ray (Biologia, 2010)

Effects of adjuvant and conidial concentration on the efficacy of Beauveria bassiana for the control of the two spotted spider mite, Tetranychus urticae - Mutimura C. Gatarayiha; Mark D. Laing; Ray M. Miller (Experimental and Applied Acarology, 2010)

Molecular detection of genomic regions associated with grain yield and yield-related components in an elite bread wheat cross evaluated under irrigated and rainfed conditions - C. Lynne McIntyre; Ky L. Mathews; Allan Rattey; Scott C. Chapman; Janneke Drenth; Mohammadghader Ghaderi; Matthew Reynolds; Ray Shorter (Theoretical and Applied Genetics, 2010)

Evaluation of pathogenicity and aggressiveness of F. langsethiae on oat and wheat seedlings relative to known seedling blight pathogens - Samuel M. Imathiu; Martin C. Hare; Rumiana V. Ray; Matthew Back; Simon G. Edwards (European Journal of Plant Pathology, 2010)

Antioxidant and oxidative stress responses of sojourners at high altitude in different climatic temperatures - Sanchari Sinha; Som Nath Singh; Mantu Saha; T. C. Kain; A. K. Tyagi; Uday Sankar Ray (International Journal of Biometeorology, 2010)

Electrogenic Cl− secretion does not occur in the ileum of the Australian common brushtail possum, Trichosurus vulpecula, due to low levels of expression of the NaK2Cl cotransporter, NKCC1 - Ray C. Bartolo; Natalie Harfoot; Mike Gill; Kristy Demmers; Bernie McLeod; A. Grant Butt (Journal of Comparative Physiology B, 2009)

Volcanology and eruptive styles of Barren Island: an active mafic stratovolcano in the Andaman Sea, NE Indian Ocean - Hetu C. Sheth; Jyotiranjan S. Ray; Rajneesh Bhutani; Alok Kumar; R. S. Smitha (Bulletin of Volcanology, 2009)

Statistical optimization of α-amylase production by Bacillus brevis MTCC 7521 in solid-state fermentation using cassava bagasse - Ramesh C. Ray; Shaktimay Kar (Biologia, 2009)

Fluorescent Recognition of Potassium and Calcium Ions Using Functionalised CdSe / ZnS Quantum Dots - Narinder Singh; Ray C. Mulrooney; Navneet Kaur; John F. Callan (Journal of Fluorescence, 2009)

Geology and geochemistry of Pachmarhi dykes and sills, Satpura Gondwana Basin, central India: problems of dyke-sill-flow correlations in the Deccan Traps - Hetu C. Sheth; Jyotiranjan S. Ray; Ranjini Ray; Loÿc Vanderkluysen; John J. Mahoney; Alok Kumar; Anil D. Shukla; Partha Das; Subhrashis Adhikari; Bikashkali Jana (Contributions to Mineralogy and Petrology, 2009)

Polygenic inheritance of canopy wilting in soybean [Glycine max (L.) Merr.] - Dirk V. Charlson; Sandeep Bhatnagar; C. Andy King; Jeffery D. Ray; Clay H. Sneller; Thomas E. Carter; Larry C. Purcell (Theoretical and Applied Genetics, 2009)

Highly efficient in vitro adventitious shoot regeneration of peppermint (Mentha x piperita L.) using internodal explants - Xiaohuan Wang; Zhenhua Gao; Yunzhen Wang; Ray A. Bressan; Stephen C. Weller; Xia Li (In Vitro Cellular & Developmental Biology - Plant, 2009)

Fusarium langsethiae pathogenicity and aggressiveness towards oats and wheat in wounded and unwounded in vitro detached leaf assays - Samuel M. Imathiu; Rumiana V. Ray; Matthew Back; Martin C. Hare; Simon G. Edwards (European Journal of Plant Pathology, 2009)

Oral contraceptives and the risk of all cancers combined and site-specific cancers in Shanghai - Karin A. Rosenblatt; Dao L. Gao; Roberta M. Ray; Zakia C. Nelson; Karen J. Wernli; Wenjin Li; David B. Thomas (Cancer Causes & Control, 2009)

Characterization of Insertion Sites in Rainbow Papaya, the First Commercialized Transgenic Fruit Crop - Jon Y. Suzuki; Savarni Tripathi; Gustavo A. Fermín; Fuh-Jyh Jan; Shaobin Hou; Jimmy H. Saw; Christine M. Ackerman; Qingyi Yu; Michael C. Schatz; Karen Y. Pitz; Marcela Yépes; Maureen M. M. Fitch; et al. (Tropical Plant Biology, 2008)

Soil lead (Pb) in residential transects through Lubbock, Texas: a preliminary assessment - Ray W. Brown; Chris Gonzales; Michael J. Hooper; Andrew C. Bayat; Ashley M. Fornerette; Tobias J. McBride; Thomas Longoria; Howard W. Mielke (Environmental Geochemistry and Health, 2008)

Luminescent Detection of ATP in Aqueous Solution Using Positively Charged CdSe–ZnS Quantum Dots - John F. Callan; Ray C. Mulrooney; Sukanta Kamila (Journal of Fluorescence, 2008)

Biocontrol Efficacy of Bacillus subtilis Strains Isolated from Cow Dung Against Postharvest Yam (Dioscorea rotundata L.) Pathogens - M. R. Swain; R. C. Ray; C. S. Nautiyal (Current Microbiology, 2008)

Genetic diversity and structure of farm and GenBank accessions of cacao (Theobroma cacao L.) in Cameroon revealed by microsatellite markers - Ives Bruno M. Efombagn; Juan C. Motamayor; Olivier Sounigo; Albertus B. Eskes; Salomon Nyassé; Christian Cilas; Ray Schnell; Maria J. Manzanares-Dauleux; Maria Kolesnikova-Allen (Tree Genetics & Genomes, 2008)

Soybean molecular linkage group B1 corresponds to classical linkage group 16 based on map location of the lf 2 gene - Thomas M. Seversike; Jeffery D. Ray; Jeffry L. Shultz; Larry C. Purcell (Theoretical and Applied Genetics, 2008)

Use of expression analysis to dissect alterations in carbohydrate metabolism in wheat leaves during drought stress - Gang-Ping Xue; C. Lynne McIntyre; Donna Glassop; Ray Shorter (Plant Molecular Biology, 2008)

Characterization of the complete genome of influenza A (H5N1) virus isolated during the 2006 outbreak in poultry in India - Koninika Ray; Varsha A. Potdar; Sarah S. Cherian; Shailesh D. Pawar; Santosh M. Jadhav; Shamal R. Waregaonkar; Anshu A. Joshi; Akhilesh C. Mishra (Virus Genes, 2008)

Anion Sensing with Luminescent Quantum Dots – A Modular Approach Based on the Photoinduced Electron Transfer (PET) Mechanism - John F. Callan; Ray C. Mulrooney; Sukanta Kamila; Bridgeen McCaughan (Journal of Fluorescence, 2008)

Ultrastructure of spore development in Scutellospora heterogama - Peter Jeffries; Louisa Robinson-Boyer; Paul Rice; Ray J. Newsam; John C. Dodd (Mycorrhiza, 2007)

Long‐Term Ecosystem Dynamics in the Serengeti: Lessons for Conservation - A.R.E. SINCLAIR; SIMON A.R. MDUMA; J. GRANT C. HOPCRAFT; JOHN M. FRYXELL; RAY HILBORN; SIMON THIRGOOD (Conservation Biology, 2007)
Data from long‐term ecological studies further understanding of ecosystem dynamics and can guide evidence‐based management. In a quasi‐natural experiment we examined long‐term monitoring data on different components of the Serengeti‐Mara Ecosystem to trace the effects of disturbances and thus to elucidate cause‐and‐effect connections between them. The long‐term data illustrated the role of food limitation in population regulation in mammals, particularly in migratory wildebeest and nonmigratory buffalo. Predation limited populations of smaller resident ungulates and small carnivores. Abiotic events, such as droughts and floods, created disturbances that affected survivorship of ungulates and birds. Such disturbances showed feedbacks between biotic and abiotic realms. Interactions between elephants and their food allowed savanna and grassland communities to co‐occur. With increased woodland vegetation, predators' capture of prey increased. Anthropogenic disturbances had direct (hunting) and indirect (transfer of disease to wildlife) effects. Slow and rapid changes and multiple ecosystem states became apparent only over several decades and involved events at different spatial scales. Conservation efforts should accommodate both infrequent and unpredictable events and long‐term trends. Management should plan on the time scale of those events and should not aim to maintain the status quo. Systems can be self‐regulating through food availability and predator‐prey interactions; thus, culling may not be required. Ecosystems can occur in multiple states; thus, there may be no a priori need to maintain one natural state. Finally, conservation efforts outside protected areas must distinguish between natural change and direct human‐induced change. Protected areas can act as ecological baselines in which human‐induced change is kept to a minimum

Fuzzy-based method for landslide hazard assessment in active seismic zone of Himalaya - P. K. Champati ray; Suvarna Dimri; R. C. Lakhera; Santosh Sati (Landslides, 2007)

Relationship between Spatial Distribution of Urban Sprawl and Species Imperilment: Response to Brown and Laband - ROBERT F. BALDWIN; JUSTINA C. RAY; STEPHEN C. TROMBULAK; GILLIAN WOOLMER (Conservation Biology, 2007)

The role of medial prefrontal cortex in context-specific inhibition during reversal learning of a visual discrimination - R. J. McDonald; N. Foong; C. Ray; Z. Rizos; N. S. Hong (Experimental Brain Research, 2007)

Structure and emplacement of the Nandurbar–Dhule mafic dyke swarm, Deccan Traps, and the tectonomagmatic evolution of flood basalts - Ranjini Ray; Hetu C. Sheth; Jyotirmoy Mallik (Bulletin of Volcanology, 2007)

Mapping of fault rupture of the 28 may 2004 iran earthquake (mw= 6.2) using satellite image - M. Sharifikia; C. S. Dubey; B. K. Sharma; M. Chaudhry; P. K. Champati Ray (Journal of the Indian Society of Remote Sensing, 2006)

RBx 7796: A novel inhibitor of 5-lipoxygenase - R. K. Shirumalla; K. S. Naruganahalli; S. G. Dastidar; V. Sattigeri; G. Kaur; C. Deb; J. B. Gupta; M. Salman; A. Ray (Inflammation Research, 2006)

Induced abortions and the risk of all cancers combined and site-specific cancers in Shanghai - Karin A. Rosenblatt; Dao L. Gao; Roberta M. Ray; Michelle R. Rowland; Zakia C. Nelson; Karen J. Wernli; Wenjin Li; David B. Thomas (Cancer Causes & Control, 2006)

Mercury Concentrations in Fish from Lake Meredith, Texas: Implications for the Issuance of Fish Consumption Advisories - William C. Mcclain; Matthew M. Chumchal; Ray W. Drenner; Leo W. Newland (Environmental Monitoring and Assessment, 2006)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)

Differential gene expression of wheat progeny with contrasting levels of transpiration efficiency - Gang-Ping Xue; C. Lynne McIntyre; Scott Chapman; Neil I. Bower; Heather Way; Antonio Reverter; Bryan Clarke; Ray Shorter (Plant Molecular Biology, 2006)

RETRACTED ARTICLE: Transgenic rice expressing Allium sativum leaf lectin with enhanced resistance against sap-sucking insect pests - Prasenjit Saha; Pralay Majumder; Indrajit Dutta; Tui Ray; S. C. Roy; Sampa Das (Planta, 2006)

Acetylcholinesterase activities in marine snail (Cronia contracta) as a biomarker of neurotoxic contaminants along the Goa coast, West coast of India - D. Gaitonde; A. Sarkar; S. Kaisary; C. D. Silva; C. Dias; D. P. Rao; D. Ray; R. Nagarajan; S. N. De Sousa; Subhodeep Sarker; D. Patill (Ecotoxicology, 2006)

Preface - Jyotiranjan S Ray; C Chakraborty (Journal of Earth System Science, 2006)

Dynamics of fine root carbon in Amazonian tropical ecosystems and the contribution of roots to soil respiration - Susan Trumbore; Enir Salazar Da Costa; Daniel C. Nepstad; Plínio Barbosa De Camargo; Luiz A. Martinelli; David Ray; Teresa Restom; Whendee Silver (Global Change Biology, 2006)
Radiocarbon ( 14 C) provides a measure of the mean age of carbon (C) in roots, or the time elapsed since the C making up root tissues was fixed from the atmosphere. Radiocarbon signatures of live and dead fine ( 40 years). Measurements of 14 C in the structural tissues of roots known to have grown during 2002 demonstrate that new roots are constructed from recent ( 14 C values in live roots most likely indicate the mean lifetime of the root rather than the isotopic signature of inherited C or C taken up from the soil. Estimates of the mean residence time of C in forest fine roots (inventory divided by loss rate) are substantially shorter (1–3 years) than the age of standing fine root C stocks obtained from radiocarbon (4–11 years). By assuming positively skewed distributions for root ages, we can effectively decouple the mean age of C in live fine roots (measured using 14 C) from the rate of C flow through the live root pool, and resolve these apparently disparate estimates of root C dynamics. Explaining the 14 C values in soil pore space CO 2 , in addition, requires that a portion of the decomposing roots be cycled through soil organic matter pools with decadal turnover time.

Marine and freshwater climatic factors affecting interannual variation in the timing of return migration to fresh water of sockeye salmon ( Oncorhynchus nerka ) - SAYRE HODGSON; THOMAS P. QUINN; RAY HILBORN; ROBERT C. FRANCIS; DONALD E. ROGERS (Fisheries Oceanography, 2006)
Interannual variation in the timing of the return migration to fresh water of adult sockeye salmon, Oncorhynchus nerka , from 46 populations throughout the species North American range was examined in a broad analysis of how timing patterns are affected by marine and freshwater conditions. Migration timing data (measured at various points along the migration, including just prior to freshwater entry, just after freshwater entry, and near the spawning grounds) were examined for correlations with sea‐surface temperatures (SST) prior to migration and to freshwater temperatures and flows during migration. Following a spring–summer period with warm SST, populations from southwestern Alaska tended to return early, Fraser River populations returned late, and populations from other regions showed no consistent patterns. Similarities between interannual timing of both nearby and distant populations indicated the presence of common or coincidental influences on timing. When riverine conditions related to timing, high flows and low temperatures were associated with late migrations, low flows and high temperatures were associated with early migrations. However, even counting stations at upriver locations showed correlations with SST. Notwithstanding some inconsistencies among the many populations examined and the indirect nature of the inferences, the results supported the hypotheses that (i) interannual variations in salmon distributions at sea reflect temperature conditions, and (ii) the date when salmon initiate homeward migration is a population‐specific trait, largely unaffected by the fish's location at sea.

A Quick appraisal of ground deformation in indian region due to the october 8, 2005 earthquake, Muzaffarabad, Pakistan - P. K. Champati ray; R. J. G. Perumal; V. C. Thakur; M. I. Bhat; M. A. Mallik; Vivek Kumar Singh; R. C. Lakhera (Journal of the Indian Society of Remote Sensing, 2005)

Purification and Characterization of Cry1Ac Toxin Binding Proteins from the Brush Border Membrane of Helicoverpa armigera Midgut - Chunyan Liao; Stephen C. Trowell; Ray Akhurst (Current Microbiology, 2005)

Accuracy assessment of InSAR derived input maps for landslide susceptibility analysis: a case study from the Swiss Alps - Lalan P. Singh; C. J. van Westen; P. K. Champati Ray; P. Pasquali (Landslides, 2005)

Evolutionary innovation: a bone‐eating marine symbiosis - Shana K. Goffredi; Victoria J. Orphan; Greg W. Rouse; Linda Jahnke; Tsegeria Embaye; Kendra Turk; Ray Lee; Robert C. Vrijenhoek (Environmental Microbiology, 2005)
Summary Symbiotic associations between microbes and invertebrates have resulted in some of the most unusual physiological and morphological adaptations that have evolved in the animal world. We document a new symbiosis between marine polychaetes of the genus Osedax and members of the bacterial group Oceanospirillales, known for heterotrophic degradation of complex organic compounds. These organisms were discovered living on the carcass of a grey whale at 2891 m depth in Monterey Canyon, off the coast of California. The mouthless and gutless worms are unique in their morphological specializations used to obtain nutrition from decomposing mammalian bones. Adult worms possess elaborate posterior root‐like extensions that invade whale bone and contain bacteriocytes that house intracellular symbionts. Stable isotopes and fatty acid analyses suggest that these unusual endosymbionts are likely responsible for the nutrition of this locally abundant and reproductively prolific deep‐sea worm.

Water quality assessment of Gautami — Godavari mangrove estuarine ecosystem of Andhra Pradesh, India during September 2001 - S. C. Tripathy; A. K. Ray; S. Patra; V. V. Sarma (Journal of Earth System Science, 2005)

Comments on the paper ?Spatial and temporal variability in excessive soil phosphorus levels in Eastern North Carolina? by Cahoon and Ensign - David H. Hardy; Richard C. Reich; M. Ray Tucker (Nutrient Cycling in Agroecosystems, 2005)

Comments on the paper ?Spatial and temporal variability in excessive soil phosphorus levels in eastern North Carolina? by Cahoon and Ensign - David H. Hardy; Richard C. Reich; M. Ray Tucker (Nutrient Cycling in Agroecosystems, 2004)

DDT and HCH Residues in Basmati Rice (Oryza sativa) Cultivated in Dehradun (India) - G. Suresh Babu; M. Farooq; R. S. Ray; P. C. Joshi; P. N. Viswanathan; R. K. Hans (Water, Air, & Soil Pollution, 2003)

Non-litter effects of elevated CO2 on forest floor microarthropod abundances - Randi A. Hansen; Ray S. Williams; David C. Degenhardt; David E. Lincoln (Plant and Soil, 2001)

Bioengineering mint crop improvement - Paola Veronese; Xia Li; Xiaomu Niu; Stephen C. Weller; Ray A. Bressan; Paul M. Hasegawa (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Influence of Timber Extraction Routes on Central African Small‐Mammal Communities, Forest Structure, and Tree Diversity - Jay R. Malcolm; Justina C. Ray (Conservation Biology, 2000)
Despite increasing pressure to harvest timber from African tropical forests, the short‐ and long‐term ecological effects of qualitative and quantitative variation in extraction practices rarely have been examined. At a site in the southwestern Central African Republic, we surveyed rodent and tree communities and vegetation structure in unlogged forest and along skid trails and secondary and primary access roads at 12 and 19 years after logging. The most important source of variation among transects was the type of logging road: primary and secondary access roads showed the greatest change and skid trails the least. An intercorrelated suite of changes occurred along the margins of the roads, including changes in rodent community composition, increases in rodent abundance and diversity, changes in the height distribution of rodent abundance, increases in understory foliage density, and decreases in sapling density and tree species richness. Ecological changes along the secondary roads were nearly as strong as those along primary roads, despite the fact that secondary roads had been abandoned immediately after logging, whereas primary roads had been traveled up to the time of the research. Continuing edge‐induced effects along graded road margins at between 12 and 19 years after logging were indicated by differences in tree species composition, sapling and tree densities, and understory density. Our results support conclusions of increased disturbance to rainforest communities with increasingly destructive road construction techniques and suggest that canopy damage rather than stem damage is the most appropriate measure of logging damage. Although minimizing the length of access roads is important in reducing ecological effects, it should not be achieved at the expense of increased canopy damage. Rodent communities appear to be an easily measured indicator of these ecological changes and may be responsive to landscape‐level changes in forest cover and degradation.

Influence of Timber Extraction Routes on Central African Small-Mammal Communities, Forest Structure, and Tree Diversity - Jay R. Malcolm; Justina C. Ray (Conservation Biology, 2000)

Endangered Species Legislation beyond the Borders of the United States - Justina C. Ray; Joshua R. Ginsberg (Conservation Biology, 1999)
Note: This month's “Issues in International Conservation” was guest edited by Justina Ray who, with Associate Editor Joshua Ginsberg, presents an overview of some global trends in endangered species legislation.

A roadmap for metapopulation research - M. Holyoak; C. Ray (Ecology Letters, 1999)
The theory of metapopulation dynamics now embraces a diversity of spatially structured populations. New and increasingly realistic models address important details of population and community dynamics. But general results are difficult to glean from such realistic models. Discovering the general behaviour of these models will require meaningful comparison of metapopulations with very diverse structures. A simple parameter space can be constructed to facilitate such comparisons. The axes defining this space determine both the structure of metapopulations and the potential for action of various persistence mechanisms. This exercise clarifies the relationship between metapopulation structure and dynamics, and illustrates future research opportunities.

Efficient plant regeneration of native spearmint (Mentha spicata L.) - Xia Li; Xiaomu Niu; Ray A. Bressan; Stephen C. Weller; Paul M. Hasegawa (In Vitro Cellular & Developmental Biology - Plant, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Interaction of the non-protein-coding developmental and stress-induciblehsrω gene withRas genes ofDrosophila melanogaster - Pritha Ray; S C Lakhotia (Journal of Biosciences, 1998)

Integrated measures of ambient toxicity and fish community diversity in Chesapeake Bay tributaries - S. Ian Hartwell; Celia E. Dawson; Eric Q. Durell; Ray W. Alden; Peter C. Adolphson; David A. Wright; Gina M. Coelho; John A. Magee (Ecotoxicology, 1998)

Relationships of chestnut species and New Zealand chestnut selections using morpho-nut characters - Nnadozie C. Oraguzie; David L. McNeil; David J. Klinac; Ray D. Knowles; J. Richard Sedcole (Euphytica, 1998)

Song rates of dark-eyed juncos do not increase when females are fertile - Russell C. Titus; C. Ray Chandler; Ellen D. Ketterson; Val Nolan, Jr. (Behavioral Ecology and Sociobiology, 1997)

Spike detection in biomedical signals using midprediction filter - S. Dandapat; G. C. Ray (Medical & Biological Engineering & Computing, 1997)

Rabies viruses infect primary cultures of murine, feline, and human microglia and astrocytes - N. B. Ray; C. Power; W. P. Lynch; L. C. Ewalt; D. L. Lodmell (Archives of Virology, 1997)

Effect of a growth hormone treatment on bone orthotropic elasticity in dwarf rats - Sean S. Kohles; Daniel A. Martinez; James R. Bowers; Arthur C. Vailas; Ray Vanderby (Annals of Biomedical Engineering, 1997)

Mechanical and biochemical analyses of tibial compartment fascia in chronic compartment syndrome - Christof Hurschler; Ray Vanderby; Daniel A. Martinez; Arthur C. Vailas; William D. Turnipseed (Annals of Biomedical Engineering, 1994)

Suppressive effect of quinalphos on the activity of accessory sex glands and plasma concentrations of gonadotrophins and testosterone in rats - A. Ray; S. Chatterjee; S. Ghosh; S. N. Kabir; A. Pakrashi; C. Deb (Archives of Environmental Contamination and Toxicology, 1991)

Selection of Lactobacillus acidophilus strains for use in ?acidophilus products? - M. C. Johnson; Bibek Ray; Tarun Bhowmik (Antonie van Leeuwenhoek, 1987)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Irrigation and fertilization effects on yield of potatoes in West Bengal - H. C. Choudhuri; A. N. Ray (American Journal of Potato Research, 1964)

Chemical weed control in potatoes in West Bengal - H. C. Choudhuri; A. N. Ray (American Journal of Potato Research, 1964)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

Leak, caused byPythium debaryanum hesse, produces typical “shell rot” of potato in Idaho - Earle C. Blodgett; W. W. Ray (American Journal of Potato Research, 1945)

Potato notes - C. Tice; W. C. Edmundson; Ray D. Hews; H. C. Moore; H. O. Werner; W. H. Martin; Daniel Dean; W. A. McCubbin; W. H. Zimmerly (American Journal of Potato Research, 1924)

Potato notes - J. T. Rosa; C. Tice; A. E. Wilkinson; B. G. Southwick; E. A. Stokdyk; Ray D. Hews; E. L. Newdick; W. Stuart; H. C. Moore; H. O. Werner; J. F. Hockey; C. L. Bailey; et al. (American Journal of Potato Research, 1924)